Optimizing MaxEnt to project habitat shifts of Idesia polycarpa var. vestita Diels, a bioenergy tree, in China under climate change scenarios - Yixuan Peng; Longcheng Jiang; Jin Wang; Rou Ma; Hua Lin; Evgeny Lopatin; Yangzhou Xiang; Hongyan Yang; Yuan Li (Biomass and Bioenergy, 2027)

Effectiveness and mechanisms of action of Bacillus velezensis GUMHT p116 against major fungal pathogens causing postharvest soft rot in kiwifruit - Xueping Wu; Zhu Li; Jianjun Lin; Zhanmei Li; Minjie Zhou; Minwei Xiang; Youhua Long; Lijuan Peng; Haixia Ding (Postharvest Biology and Technology, 2026)

From buffalo to human: Klebsiella pneumoniae in high-somatic cell count milk as an overlooked link in the one health chain - Zhifei Wei; Yifei Xiang; Xuelian Mo; Wenjing Li; Erqiang Wang; Changhua Lin; Jiazhou Wei; Yulian Xi; Yuying Liao; Zhengmin Liang; Zhiran Xu; Jiakang He (International Journal of Food Microbiology, 2026)

Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Experimental study on mechanical properties of double-layer damped liquid storage tanks with various isolation devices - Xiang Li; Lei Xu; Fa Yang; Li-jie Zhu; Bo-lin Wang; Zheng Lu (Soil Dynamics and Earthquake Engineering, 2026)

Erratum to “Spatial metabolomics reveals tissue-specific oxidative imbalance and sulfur amino acid metabolism during postharvest deterioration of goji berry (Lycium barbarum L.)” [Postharv. Biol. Technol. 240 (2026) 114463] - Hanxi Li; Long Xiang; Xintong Wang; Yukun Xi; Fu Wang; Lin Chen; Hongping Chen (Postharvest Biology and Technology, 2026)

Metagenomic indications of potential pathogen-associated and antibiotic resistance risks following UV–chlorine disinfection in sprout production - Yufei Wei; Lin Zhu; Xiangfu Jin; Huangli Yao; Shanshan He; Pu Feng; Feihong Yu; Yulu Xiang; Zhiheng Li; Shanying He (Environmental Pollution, 2026)

A dual mechanical tuning framework for rigid pillared elastic metamaterials: Geometric reconfiguration and controllable prestress - Zu Shao; Tong Cheng; Yi Zhang; Wei Zhong Jiang; Zhu Kun Mi; Xiang Jie Wei; Xin Guo; Wang Lin Xiong; Kai Hao Lin; Chuang Li; Shu Hao Song; Cheng Shen; et al. (Engineering Structures, 2026)

Immobilizing MIL-9 in PVDF spheres for durable and efficient peroxymonosulfate activation toward antibiotic degradation - Xing-Lin Lv; Peng Wang; Xiang-Yu Li; Fei Wang; Zi-Yu Jia; Miao Chang; Xin Jiang; Zhao-Yi Liu; Xiao-Hong Yi; Anping Wang; Jiguang Deng; Chong-Chen Wang (Chemical Engineering Journal, 2026)

Extracellular polysaccharide-facilitated selenium nanoparticle assembly and metabolic reprogramming support efficient selenite biotransformation by ARTP-mutagenized Lactiplantibacillus plantarum Vse252 - Lihui Tan; Xinyan Wang; Lin Hu; Xiang Gen; Shirui Yu; Xue Li; Xinyu Yan; Bo He; Jun Zhang; Yongzhong Wang; Hengqian Lu (Bioresource Technology, 2026)

Breaking the channel barrier: same-fluorescence, different-Tm probe strategy enables seven-target respiratory virus detection on a six-channel PCR platform within 20 minutes - Yang Li; Yi-Nuo Zhao; Xiang Li; Ting Sun; Lin-wei Zhu; Miao-jin Zhu; Li-Guo Liang; Hang-ping Yao (Analytica Chimica Acta, 2026)

Progressive fluorescence amplification of molecular rotors via G-run-length engineering of G-rich DNA scaffolds - Ruo-Yao Cui; Yu-Chao Cao; Yi-Xuan Gu; Ling-Li Zhao; Xu-Yang Shen; Ying Liu; Ying-Lin Zhou; Xin-Xiang Zhang (Analytica Chimica Acta, 2026)

Spatial metabolomics reveals tissue-specific oxidative imbalance and sulfur amino acid metabolism during postharvest deterioration of goji berry (Lycium barbarum L.) - Hanxi Li; Long Xiang; Xintong Wang; Yukun Xi; Fu Wang; Lin Chen; Hongping Chen (Postharvest Biology and Technology, 2026)

BcSak1-mediated adaption to low temperature in Botrytis cinerea represents optional targets for management of cold-tolerant diseases on harvested fruits - Ziwei Su; Yuxuan Lin; Xinyi Long; Jiaxi Zhang; Yin Li; Chuanxi Zhu; Wenjin Yan; Congcong Wang; Yiwen Wang; Junwei Zhao; Xiang Li; Aruppillai Suthaparan; et al. (Postharvest Biology and Technology, 2026)

Deformation and global buckling analysis of long-distance shallowly embedded subsea pipeline under strike-slip fault displacement - Zhenmian Li; Xinfeng Pang; Zhengle Xiang; Haoxi Zhang; Zeheng Li; Changxi Wang; Jiacheng Lin (Ocean Engineering, 2026)

Reprogramming oily water separation with Janus membranes: From asymmetric fabrication to engineering perspectives - Mingyi Ying; Bisheng Li; Jiaheng Teng; Xiang Cai; Cheng Chen; Leihong Zhao; Hongjun Lin (Journal of Environmental Chemical Engineering, 2026)

Urban sidewalk detection via a cross-view joint segmentation method using satellite and street-view imagery - Yi Lin; Weijia Li; Jinhua Yu; Junyan Ye; Jun He; Xiang Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Experimental study on impingement and combustion characteristics of two opposing sprays with start of injection separation - Lin Xiang; Xiaojie Li; Liang Wang; Yuhan Huang; Haojin Li; Qingwen Zeng; Hong Li; Zhaowen Wang (Fuel, 2026)

Integrated metabolomic, transcriptomic, and proteomic analyses reveal changes in the non-volatile metabolite profile of LED light–withered oolong tea - Qiuming Li; Yucheng Zheng; Hongzheng Lin; Yongpeng Wu; Jihang He; Xinru Yu; Mingxing Ling; Xiang Li; Jinke Lin; Zhilong Hao; Xinchao Wang; Yun Sun (Food Chemistry, 2026)

From black box to transparency: Explainable artificial intelligence driven origin identification of Xinjiang Nilka black bee honey - Xiao-Hui Sun; Lin-Hua Shi; Xiang-Shuai Li; Xiu-Ying Tang; Hong-Song Ren; Sheng-Hong Liu (Food Chemistry, 2026)

Investigations on ballistic behaviour of additive manufactured 316L stainless steel corrugated sandwich panels filled with ultra-high performance geopolymer concrete - Jian Liu; Cunyi Li; Guobin Li; Sihao Lin; Ming-Xiang Xiong; Jianguang Fang (Engineering Structures, 2026)

Thermal response analysis of permeable energy piles with different backfill materials under seepage conditions based on equivalent permeability characterization - Zhipeng Geng; Qiqi Wu; Jinli Lin; Xiang Li; Yongyi Li; Guoxiong Mei (Energy and Buildings, 2026)

Micro-bipolar interface in catalyst layers for polymer electrolyte membrane fuel cell - Yunqi Li; Xinkai Zhang; Hanfei Xie; Qi Zhang; Xiaofang Shen; Yuheng Zhou; Haining Wang; Yiyang Liu; Jin Zhang; Wen Li; Jiashuo Fu; Lin Zhuang; et al. (Chemical Engineering Journal, 2026)

CO2-triggered multiresponsive polymers for efficient gas channeling control: Conformational changes and dynamic network synergy - Wei Xiang; Jia Chen; Yunbo Dong; Yue Wen; Zizhao Wang; Lin Li; Caili Dai (Chemical Engineering Journal, 2026)

Illicium verum polysaccharide targets fimbriae and flagella to disrupt biofilm and inhibit multidrug-resistant Escherichia coli proliferation - Yifei Xiang; Erqiang Wang; Xuelian Mo; Zhifei Wei; Zhiran Xu; Wenjing Li; Changhua Lin; Yanwen Zhang; Chunxia Ma; Bin Zheng; Ziyang Li; Chengzhi Liu; et al. (Carbohydrate Polymers, 2026)

Study on the friction properties of compacted snow layers and influencing factors - Chunyan Li; Chao Jiang; Tao Chen; Qinghua Huang; Xiang-Lin Gu (Cold Regions Science and Technology, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Sludge-derived biochar-activated peroxymonosulfate as a waste-to-resource pretreatment for sustainable membrane fouling control: Adsorption-oxidation interplay and thermodynamic insights - Mingjing Xie; Biyan Wang; Jiaqi Liu; Xiao Xu; Hanmin Zhang; Meijia Zhang; Xiang Cai; Leihong Zhao; Bisheng Li; Liguo Shen; Jiaheng Teng; Hongjun Lin (Journal of Cleaner Production, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Stress Superposition Mechanism and Engineering Calculation Method for Compacted Snow Runways Under Aircraft Multi-wheel Loads - Chunyan Li; Tao Chen; Chao Jiang; Qinghua Huang; Xiang-Lin Gu (Transportation Geotechnics, 2026)

Halorubrum marinum sp. nov., Halorubrum rarum sp. nov., Halorubrum wangae sp. nov., Halorubrum shenae sp. nov., and Halorubrum zhoui sp. nov., halophilic archaea from coastal tidal flats, a saline lake, and a marine solar saltern - Qing-Di Li; Yang-Yang Wang; Chidiebele Nwankwo; Yao Hu; Xin-Yue Dong; Jing Hou; Xiang-Dong Chen; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Environmental DNA metabarcoding complements bottom trawling and detects fish species beyond recorded ranges in the Chukchi Borderland, Central Arctic Ocean - Hai Li; Fang Yang; Xiang Zhang; Ran Zhang; Rui Wang; Xing Miao; Shigang Liu; Puqing Song; Yuan Li; Longshan Lin (Marine Environmental Research, 2026)

Directional disparity between oysters and mud snails in modulating marine carbon sequestration - Zhou Zhang; Xuan Dong; Yu-Jia Lei; Zhi-Yong Guo; Shuang-Jie Tian; Chang-Lin Li; Miao-Jun Pan; Xiang-Li Tian; Yun-Wei Dong; Jing-Yu Li; Shuang-Lin Dong (Journal of Environmental Management, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

From molecular interactions to macroscopic functions: Dynamic cross-linked carboxymethyl cellulose as a strategic modifier for soy protein isolate - Can Zhao; Liangfeng Ma; Ziqiao Lin; Lifen Li; Junchao Huang; Yang Liu; Yingting Zhao; Qisen Xiang; Yuting Tian (Carbohydrate Polymers, 2026)

Ultrasensitive biosensor for near femtogram-level detection of interleukin-1 beta in saliva - Jiayi Liu; Miao Xie; Yufei Tang; Ruotong Mai; Jinhao Zhou; Yixin Zhou; Xingrui Li; Jinjie Wen; Wei Huang; Lin Xiang (Analytica Chimica Acta, 2026)

Characterization of a novel Era-homolog (AtERG1) in Arabidopsis that is essential for chloroplast development - Yi Lin; Shuangyuan Jia; Chenchen Zhang; Shanshan Chen; Han Xiang; Jiaqi Chen; Ying Yang; Jiawei Chen; Ming Li; Jinwen Liu (Journal of Plant Biochemistry and Biotechnology, 2026)

Adsorption and ligand-to-metal charge transfer (LMCT)-driven photodegradation of PFOA/PFOS by iron-based materials: Mechanistic insights and environmental risk analysis - Tao Jian; Bisheng Li; Cheng Chen; Leihong Zhao; Xiang Cai; Hongjun Lin; Xiaohong Guan (Critical Reviews in Environmental Science and Technology, 2026)

A domain-enhanced multi-agent framework for trustworthy literature screening in water research - Runzhi Wang; Xinlu Lin; Baoyi Zhong; Jiaxuan Li; Ruixing Huang; Yu Huang; Yajuan Cai; Chotiwat Jantarakasem; Yang Xiang; Konstantinos Plakas; Jun Ma; Yumeng Zhao (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Ship berthing path planning and adaptive MPC control based on improved A∗ and B-spline optimization - Xiang Zhao; Zhenyang Xu; Lin Chen; Xiaoyan Li; Zhen Su (Ocean Engineering, 2026)

Seasonal variation of fish biodiversity in Xisha Islands based on dual-marker eDNA metabarcoding - Shengming Deng; Yuguo Ye; Min Liu; Bai-an Lin; Chengdan Ma; Yifeng Xu; Yongcan Zhou; Shifeng Wang; Weiliang Guo; Huilong Ou; Xiang Zhang; Jianlong Li (Marine Environmental Research, 2026)

Industrial waste salt pyrolysis toward zero liquid discharge: Enabling efficient organic removal and resource recovery - Zhi-Bo Li; Xiang-Lin Chang; Juan Xie; Rong Chen; Xiaochang C. Wang; Bao-Shan Xing (Journal of Water Process Engineering, 2026)

Preparation of a MOF-derived Mn-Ti catalyst and its simultaneous removal of NOx and toluene: Strong metal-support interaction and Lewis acid sites - Yongchao Zhong; Dan He; Qiangwei Lu; Lu Wang; Yunkuo Luo; Dongliang Zhang; Chaochao Li; Lin Li; Fengying Li; Xiang Tu; Chenglong Yu (Journal of Environmental Chemical Engineering, 2026)

Efficient photocatalytic degradation of acetamiprid via Fe2O3/Fe-TCBPE activating peroxymonosulfate - Chenchen Li; Zhourui Wu; Rui Xu; Tai Xiang; Lin Tian; Yong Zhang (Journal of Environmental Sciences, 2026)

A review of catalysts used in microwave-assisted pyrolysis of waste plastics - Wuwan Xiong; Biyi Zhang; Jialing Zhu; Meiyun Lai; Zishan Feng; Yijun Chen; Haisheng Lin; Bo Zhang; Yang Zhang; Xiang Li; Fei Li (Fuel, 2026)

Quantitative analysis of spray morphology and shock wave structures in supercritical methanol spray - Xiaojie Li; Liang Wang; Yi Hu; Lin Xiang; Ruiqi Wang; Qi Xiao; Zhaowen Wang (Fuel, 2026)

Environmental factors drive rutin accumulation through a synergistic network promoting flavonoid biosynthesis and suppressing hydrolysis in tea plants (Camellia sinensis) - Ping Xiang; Puzhen Xu; Yuanyuan Li; Marat Tukhvatshin; Qiufang Zhu; Huaxiu Gong; Yingying Wei; Jinliang Li; Qiliang Peng; Xuan Zhao; Jianghong Liu; Jinke Lin (Food Chemistry, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Chemical constituents from the roots of Illigera celebica - Si-Feng Yang; Lin-Wen Yi; Qiu-Xia Huang; Xing-Meng Luo; Xiao-Bing Su; Lin Hu; Wen-Ting Li; Xiang-Zhong Huang; Meng-Yuan Jiang (Natural Product Research, 2026)

Opening the window to the solar-driven world of MXenes: Mechanisms, synergistic strategies, and emerging applications for sustainable environmental purification - Xiao Zhang; Yingzi Du; Wenzhe Yu; Mingzhu Zhou; Xiang Cai; Leihong Zhao; Hongjun Lin; Bisheng Li (Critical Reviews in Environmental Science and Technology, 2026)

Neural network approach for predicting outcomes of external cephalic version for breech presentation: a retrospective cohort study - Yuting Xiang; Wenjian Yang; Haote Han; Haixia Lin; Wanhua Wu; Suran Huang; Hao Wang; Ning Hu; Zhongjun Li (Journal of Zhejiang University-SCIENCE B, 2026)

Advances in oral delivery systems for alpha-linolenic acid: mechanisms, bioavailability, and applications in functional foods - Fazhan Zhong; Qianchun Deng; Shangwen Chen; Rui Fang; Yawen Huang; Dengfeng Peng; Xia Xiang; Yashu Chen; Li Chen; Xiao Lin; Ziyu Deng (Critical Reviews in Food Science and Nutrition, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Clean heating transition in China: Technological innovation, residual emission burden, and regional inequality in northern cities - Linyan Li; Yunlong Wu; Li Zhang; Huili Wang; Jieyi Li; Lin Xiang; Xiurong Hu; Jiaxuan He; Ling Jin; Xiaojun Chen; Hui Xu; Yu Lei (Sustainable Production and Consumption, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

The domestication-associated WHP10 tandem cluster of amino acid transporter genes enhances whole-plant protein accumulation in maize - Wenhao Li; Youliang Li; Xiang Lin; Ruilin Chen; Wenjing Li; Chong You; Di Chen; Lulu Gao; Xiaoling Li; Shiqi Luo; Yunlong Li; Yuhua Long; et al. (Molecular Plant, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Corrigendum to “A review of catalysts used in microwave-assisted pyrolysis of waste plastics” [Fuel 418 (2026) 138805] - Wuwan Xiong; Biyi Zhang; Jialing Zhu; Meiyun Lai; Zishan Feng; Yijun Chen; Haisheng Lin; Bo Zhang; Yang Zhang; Xiang Li; Fei Li (Fuel, 2026)

Optimizing carbon-cement electrode performance through construction of a strong skeleton-highly connected pore structure based on ettringite - Xiang Lin; Xujiang Wang; Guanjie He; Jian Song; Yanmei Cheng; Jie Chen; Xin Shu; Deqiang Sun; Jingwei Li; Zhijuan Hu; Wenlong Wang (Chemical Engineering Journal, 2026)

Polyacrylamide based hydrogel with high temperature and salinity tolerance: the role of aminated distilled spent grain - Xue-Li Long; Kang-Lin Chen; Hong-Ke Yang; Hong-Li Dong; Hong-Kui He; Li-Chun Dai; Zu-Guo Yang; Zhi-Xiang Xu (Biomass and Bioenergy, 2026)

Enhancing microalgal bioremediation and bioproduction with chemical additives: Mechanisms and strategic perspectives - Yongteng Zhao; Shiyu Lin; Qingqing Li; Feiyan Huang; Xiang Wang; Lei Zhang; Xuya Yu; Lei Yu (Algal Research, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Transcriptome sequencing of the Epinephelus lanceolatus reveals the potential physiological responses of mesopelagic fishes to light stress from deep-sea mining - Xiang Zhang; Tianci Wang; Yuan Li; Puqing Song; Shigang Liu; Yuzhuo Liao; Hai Li; Longshan Lin (Marine Pollution Bulletin, 2026)

Mechanistic responses of coccolithophores to exposure to the marine pollutant atrazine - Xiang-Wu Chen; Yi-Tong Huang; Yue-Tao Song; Zhuo-Fan Li; Xue-Ling Huang; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Redefining solid–liquid interface probing via contact electrification-driven paradigm - Xiang Li; Zhong Lin Wang; Di Wei (Science Bulletin, 2026)

Deep visual multi-omics reveals intra-tumor heterogeneity of gene expression and immunophenotype in colorectal cancer - Shijun Lei; Wanshan Ning; Hongyan Zhang; Qun Chen; Luming Xu; Shaobo Tian; Xiaoqiong Li; Wenyu Liu; Mengxi Xiang; Feng Liu; Guobin Wang; Lin Wang; et al. (Science Bulletin, 2026)

DCC and ADP modulate the disease progression in postharvest longan caused by Phomopsis longanae Chi in relation to ROS metabolism and cell wall integrity - Xiang Gao; Xiaoxuan Wang; Wenjing Lin; Huili Zhang; Ruiling Zhuo; Yihui Chen; Boqiang Li; Shiping Tian; Hetong Lin; Yifen Lin (Postharvest Biology and Technology, 2026)

A novel endophytic Penicillium sp. JL76001 and its metabolite sclerotiorin: A multi-target and sustainable strategy for biocontrol of tomato Fusarium wilt - Xuecheng Sun; Yutong Feng; Pan Xiang; Fudong Wang; Weizhuo Tang; Sai Jiang; Meng Su; Zixian Zeng; Shunxiang Li; Lin Jiang (Pesticide Biochemistry and Physiology, 2026)

Morphological variations of rugose coral Keyserlingophyllum from Baoshan, southwestern China and their palaeoecological implications - Lu Li; Xiang-Dong Wang; Wei Lin; Le Yao (Palaeoworld, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

Experimental and theoretical study on the ultimate bearing capacity of U-shaped steel-concrete composite cap beams - Heng Liu; Lin Xiao; Xing Wei; Xiang Li; Jian Ren; Huijun Wang (Engineering Structures, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Targeting complement and coagulation cascades with Buyang Huanwu Decoction attenuates acute inflammation and enhances neuroprotection in spinal cord injury - Dezun Ma; Xinyu Xie; Yijun Ma; Hui Yan; Haoyuan Yin; Xue Tan; Yan Li; Xinpei Lin; Yuexin Huang; Xiang Wu; Zhihao Zhou; Chenglin Yang; et al. (Science China Life Sciences, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Non-progressive orogenesis of the Southern Tibetan Plateau - Xiaoyu Guo; Hengcheng Ying; Lin Chen; Rui Gao; Xiaofan Deng; Zhanwu Lu; Hongda Liang; Bo Xiang; Michael Murphy; Wenhui Li; Xiao Xu (Science Bulletin, 2026)

Toward a “green revolution” for Tartary buckwheat through ideotype breeding - Wei Li; Hao Lin; Xiang Lu; Yang Liu; Yuqi He; Zhirong Wang; Kaixuan Zhang; Muriel Quinet; Sun-Hee Woo; Dagmar Janovská; Nóra Mendler-Drienyovszki; Mateja Germ; et al. (Molecular Plant, 2026)

A transformer-reinforcement learning framework integrating acoustic thermometry for multi-pollutant prediction and control in a full-scale WtE plant in China - Yuxuan Ying; Linyi Chen; Hanqing Yang; Tianyi Zhu; Weiwei Cao; Zhenwei Yang; Hongyu Sun; Jinghao Ye; Yu Liu; Yunhua Zhao; Weiya Jin; Mi Yan; et al. (Journal of Cleaner Production, 2026)

Green synthesis of glycerol carbonate from glycerol and CO2 using a polymeric ionic liquid catalyst: An experimental and theoretical study - Yi-Lin Lee; Yu-Chi Kao; He-Xiang Xu; Shun Tsunekawa; Masaaki Yoshida; Yi-Pei Li; Chechia Hu (Journal of Cleaner Production, 2026)

Mechanistic insights into the effects of roasting on heat-induced hazard formation and lipid oxidation stability in camellia seeds - Tongqiang Chen; Xiaojuan Wu; Jun Xiang; Helin Li; Kailong Li; Haizhi Wu; Wenjie Tang; Can Li; Qinlu Lin; Wei Wu (Food Chemistry, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

A novel double-layer composite material with excellent radiative cooling and thermal management for electronic devices - Haoxin Lv; Haixuan Liu; Jiahui Lin; Jintao Huang; Hanlin Xie; Xiaofeng Li; Yonggang Min; Xiang Lu (Chemical Engineering Journal, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Structural determinants of gelation kinetics in rambutan seed starches: Implications for enhanced precision in 3D food printing - Rui He; Yuxuan Li; Xiaoyu Lin; Bo Xu; Xiang Huo; Weiming Zhang; Tao Yang; Geng Zhong; Fengwei Xie; Ying Chen (Carbohydrate Polymers, 2026)

Preparatory Activity Indexes Motor Memory in the Motor Cortex - Xiao–Lin Shen; He–Xin Zhao; Yu–Hao Xiao; Yong–Xiang Wang; Li–Zhang Zeng; Hong–Yan Geng (Neuroscience Bulletin, 2026)

Diosmetin, an active ingredient of Schizonepeta tenuifolia, alleviates acne by regulating inflammation and oxidative stress - Yu Pan; Rui Sun; Elizabeth Rosalind Thomas; Shi Pan; Linli Yang; Wenjun Wang; Lin Chen; Xiang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Experimental Study on Shear Anisotropy and Anchoring Mechanism of Fractured Rock Masses - Shuguang Zhang; Jiamian Lin; Wenbo Liu; Xiang Huang; Dipeng Zhu; Wenwu Ou; Shutian Zhao; Yipin Liu; Yingbo Li (Geotechnical and Geological Engineering, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Experimental and numerical investigation on seismic behavior of existing masonry corner walls strengthened with external thin concrete columns - Guo-Lei Li; Qian-Qian Yu; Xiang-Lin Gu; Xiang Li; Hong Zhang (Bulletin of Earthquake Engineering, 2026)

The Study on the Application of Time-Lapse Double-Difference Tomography Theory in the 3D Velocity Structure Distribution of Tunnel Surrounding Rock - Hongyun Yang; Zhiming Zhang; Xiang Wang; Yifei Wu; Zhi Lin; Yong Li; Xiang Chen; Wanlin Feng; Chuandong Jiang (Rock Mechanics and Rock Engineering, 2026)

Excitation mechanisms and vibration response of a horizontal elbow in gas-liquid two-phase flow - Yitong Fu; Xiang Li; Bolun Ding; Yiran Duan; Lin Ding (Ocean Engineering, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Effects of co-existing substances on phosphorus recovery from swine wastewater via struvite crystallization with a carbon felt cathode - Ying Xiang; Weike Lin; Shuoshi Guo; Jinfeng Wei; Peng Li; Jin Li; Fang Wang (Journal of Environmental Management, 2026)

Insights into the molecular transformation pathways of humus during co-composting of bagasse pith and buffalo manure using compound microorganisms (LXB) - Shiyuan Niu; Binfeng Lin; Yu Zhang; Hongquan Xiang; De Ding; Zhi Huang; Jianbin Li (Journal of Environmental Chemical Engineering, 2026)

Co-addition of alkali lignin and microbial agents drives humic substances assembly by regulating precursor conversion and microbial metabolism in composting - Hongquan Xiang; Shiyuan Niu; De Ding; Binfeng Lin; Yu Zhang; Yongwei Zhu; Shiqiang Li; Ziyang Zhao; Jianbin Li; Zhi Huang (Journal of Environmental Chemical Engineering, 2026)

Fouling behavior and cleaning strategy during treatment of practical refractory organic wastewater using anaerobic ceramic membrane bioreactor - Ruihui Chen; Lixiu Shi; Xinsen Li; Hongming Yang; Sheng Xiang; Mohd Fadhil MD Din; Eli Hendrik Sanjaya; Lu Peng; Zhengwang Wu; Chengcheng Lin; Hong Chen (Journal of Environmental Chemical Engineering, 2026)

Revealing the metabolic mechanism of enzymatic hydrolysis products of boletus edulis bull.: Fr. Based on random forest integration multi-omics - Ningjing Guo; Xiang Li; Ya Dai; Xue Li; Qian Yao; Hua Lin; Mingjing Song (Food Chemistry, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

Corrigendum to “Nitrogen losses trade-offs through layered fertilization to improve nitrogen nutrition status and net economic benefit in wheat-maize rotation system” [Field Crops Res. 312 (2024) 109406] - Changhong Liu; Shengyan Pang; Xiufeng Li; Yongqiang Li; Jinwei Li; Ruoling Ma; Xiang Lin; Dong Wang (Field Crops Research, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

Sex Differences in Vigilance Functions of Golden Snub-nosed Monkeys (Rhinopithecus roxellana): Females Prioritize Antipredator Vigilance While Males Focus on Social Vigilance - Hui Yu; Chi Zhang; Jinhuang Lin; Ruiyuan Li; Hui Yao; Wanji Yang; Ali Krzton; Yang Yu; Zuofu Xiang (International Journal of Primatology, 2026)

Muscle-specific transcriptomic and metabolomic signatures reveal heterogeneous aging trajectories and altered intercellular communication in male murine skeletal muscle - Caifen Guo; Xinqiang Lan; Chunping Huang; Xiang Wang; Dongqin Zhang; Lin Zeng; Qiquan Wang; Yang Xiang; Jian Li (Biogerontology, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Construction of a coccolithophore database platform for ecological and molecular applications - Xue-Ling Huang; Yi-Xin Xiong; Shuang Yu; Xiang-Wu Chen; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Effects of in-situ stress direction and orientation of structure planes on rockburst generation in deep tunnels: 56 case studies - Ben-Guo He; Xiang-Rui Meng; Bo Lin; Hong-Pu Li (Tunnelling and Underground Space Technology, 2026)

Turtle shell as a health food ingredient: a review of global utilization, nutritients, health benefits, and functional food potential - Mengying Ren; Jianfeng Lu; Zhengrong Li; Tao Ye; Yuan Song; Huizi Lu; Nianyue Lai; Xudong Xiang; Li Yang; Lin Lin; Shaotong Jiang; Yun Wang (Trends in Food Science & Technology, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Delineating fish ecological corridors in a subtropical bay using eDNA metabarcoding: A case study from Xiamen Bay, China - Hai Li; Fang Yang; Xiang Zhang; Yuzhuo Liao; Yuan Li; Puqing Song; Shigang Liu; Longshan Lin (Regional Studies in Marine Science, 2026)

Spatial-X fusion for multi-source satellite imageries - Jiang He; Liupeng Lin; Zhuo Zheng; Qiangqiang Yuan; Jie Li; Liangpei Zhang; Xiao xiang Zhu (Remote Sensing of Environment, 2026)

SiGSTU18 positively regulates saline-alkali tolerance in foxtail millet through glutathione metabolism and glutamic acid-mediated alleviation of oxidative stress and ion toxicity - Yun Li; Yuxue Zhao; Fuxing Xiang; Fangying Chen; Yanrui Xu; Xiaohu Lin; Jihan Cui; Yucui Han (Plant Science, 2026)

A hybrid AWQMIX-MGT algorithm integrating deep reinforcement learning and collaborative optimization strategies for ship equipment and pipe layout design - Hongshuo Zhang; Yanyun Yu; Qiang Li; Dechen Liu; Qi Men; Xiang Liu; Yan Lin (Ocean Engineering, 2026)

Macrophage-derived exosome as bioengineered nanotherapeutics for silica-induced reproductive dysregulation - Zitong Zhang; Jiahua Meng; Zhen Chen; Xiang Yun; Ning Li; Qiang Li; Jiaqi Tian; Huiyu Sun; Zengfeng Li; Fei Li; Shuyin Duan; Lin Zhang (Journal of Hazardous Materials, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Irradiation co-succinylation modification of caprine casein: Impact on physicochemical properties, molecular structure, and functional properties - Jing Xi; Huiyu Han; Rong Bai; Madina Aitmagambetova; Siying Wang; Shengqi Jiang; Hongqing Nie; Lin Li; Xiang Ye; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Pea proteins prepared by self-coacervation: Physicochemical characterization and emulsifying properties - Zhuojia Lin; Jialing Chen; Zixi Liu; Xiang Li; Zhili Wan; Xiaoquan Yang (Food Hydrocolloids, 2026)

The microbial response to biodegradable polylactic acid microplastics during anaerobic fermentation of waste activated sludge - Jie Chen; Jinjing Xiang; Maoli Hu; Yafei Zhang; Li Gu; Qiang He; Lin Li (Environmental Research, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Hetero-folded hBN/graphene with ultrahigh thermal conduction and electrical insulation for reliable thermal management - Han Zhao; Pengyu Zhang; Jingran Guo; Dizhou Liu; Shixuan Dang; Duola Wang; Hongxuan Yu; Jiali Chen; Chuanyun Song; Yuanpeng Deng; Yingde Zhao; Cong Li; et al. (Chemical Engineering Journal, 2026)

Chiral CD@Ag2O nanoparticle-mediated highly efficient antibacterial activity based on synergistic multi-pathway interactions - Xiang Li; Qi Ding; Si Li; Junru Li; Heng Zhang; Shan Sun; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Bayesian inference on fermentation kinetics: Comparative analysis with frequentist approach - Xiang Li; Yen-Han Lin (Bioresource Technology, 2026)

Shifting from biotic to abiotic drivers of urban microbial multifunctionality under drought and rehydration - Chenhong Peng; Anqi Sun; Xinyuan Li; Yilong Hao; Yifang Zhang; Qian Xiang; Qing-Lin Chen (Science China Life Sciences, 2026)

Visualizing the Landscape and Evolution of Phosphorus Research in Saline-Alkali Soils by Scientometric Analysis - Pingping Zhang; Yuhang Li; Lin Liao; Junna Hu; Genmei Wang; Huanchao Zhang; Jian Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Soybean Hyperspectral Leaf Area Index (LAI) Estimation Based On Soil-vegetation Separation Algorithm and Derivative Spectroscopy - Nai-ning Zhong; Yu-lin Liu; Yi-zheng Zhao; Yi-xuan Mei; Hao-lin Shen; Xin-Zhou Lei; Yu-ning Wu; Juan-li Ju; Youzhen Xiang (Journal of Soil Science and Plant Nutrition, 2026)

The role of KPNA3 in multiple myeloma: implications for targeting nuclear import - Hongmei Luo; Ziyue Mi; Jingcao Huang; Jingjing Wen; Siyao He; Haonan Yang; Yue Zhang; Linfeng Li; Xiang Liu; Xinyu Zhai; Fangfang Wang; Xinai Gan; et al. (Apoptosis, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Mechanistic Links Between Suspended Sediment Dynamics and Metal Partitioning Under Tidal Forcing: A Case Study of Quanzhou Bay - Yanbin Fan; Yunhai Li; Yunpeng Lin; Shangshang Yang; Zhijie Chen; Xiang Cao; Chenyang Wang; Shanshan Zhang; Jinzeng Jiang; Mingyang Jiang; Kaichao Wan (Journal of Marine Science and Engineering, 2026)
The coupling of physical transport and phase-transfer processes represents a fundamental mechanism governing metal cycling in estuarine systems under tidal oscillations. Taking Quanzhou Bay as a model system, we conducted continuous observations and sample collection at the river channel (Q1), the turbidity maximum zone (Q2), and the outer bay channel (Q3). The metals (Al, Ti, Ba, Cu, Mn, and Zn) were measured by ICP-MS to systematically investigate the distribution, transport, and inter-media transfer across multiple water layers under varying estuarine processes. Our findings demonstrate that particulate metal concentrations in Quanzhou Bay exhibit strong synchrony with suspended sediment concentrations (SSC) over tidal cycles, displaying a distinct sediment-following pattern controlled by alternating end members. Particulate metal fluxes during flood and ebb-tides generally followed the hierarchy Q1 > Q2 >> Q3. Notably, stations Q1 and Q2 were dominated by flood-tide fluxes with net transport directed landward, whereas Q3 was characterized by ebb tide dominance with net flux directed seaward—revealing a spatial division of labor between “inner bay retention/reallocation” and “outer bay channel export”. In contrast, dissolved metals exhibited marked element-specific responses to tidal forcing: Al and Ti increased during flood tides at stations Q1 and Q2, while Ba and Cu showed opposite trends, and Mn and Zn displayed more conservative behavior. Concurrently, solid/liquid partition coefficient (logKd) values for Al, Ti and Ba, Cu exhibited inverse patterns over tidal cycles, suggesting divergent adsorption–desorption regulation under identical hydrodynamic conditions that drives differential phase-transfer dynamics. These disparities likely reflect intrinsic chemical properties and source variations among the elements. This study elucidates, at the tidal timescale, the coupled processes of “alternating end-member control—estuarine filter modulation—concurrent channelized export and inner bay retention” in Quanzhou Bay, providing critical process-level insights for metal flux quantification and bay pollution remediation initiatives in an ecological restoration project.

Widespread depletion of inorganic carbon in Europe's topsoil revealed by spatiotemporal digital soil mapping - Chenxu Zhu; Lin Yang; Ren Wei; Xiang Li; Chenconghai Yang; Wenkai Cui; Chenghu Zhou (Soil and Tillage Research, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Concurrent removal of cetirizine hydrochloride and biodiesel accumulation in Chlorella vulgaris - Wen-Bo Yan; Zhong-Hong Zhang; Guo-Hui He; Jia-Xuan Tang; Hui-Lin Guo; Yi-Fan Zhan; Wei-Dong Yang; Hong-Ye Li; Xiang Wang (Journal of Hazardous Materials, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Dissolved-O2–driven Mn single-atom enzyme for colorimetric detection of glutathione in food - Lin Wang; Yue Wang; Xiao-Jie Shi; Tian-Shun Song; Xiang-Ling Li; Jing-Jing Xie (Analytica Chimica Acta, 2026)

Integrated single-cell multi-omics profiling reveals a senescence-associated hematopoietic landscape and regulatory network in aging bone marrow - Guoyang Zhang; Weixuan Lin; Linghuan Guo; Ziyun Li; Yu Xiang; Luo Wang; Xiaoyu Yan (Biogerontology, 2026)

Extreme drought amplifies the dominant role of Secchi depth on the underwater light environment: evidence from Poyang Lake - Jianying Chao; Xiaowen Lin; Xiaodong Wu; Jian Li; Xuguang Ge; Zhenni Gao; Chenxin Zhong; Zian Xiang; Lishuai Zhang (Environmental Monitoring and Assessment, 2026)

Pooled data from phase 3 clinical trials comparing the clinical activity of ceftolozane/tazobactam versus meropenem for the treatment of complicated intra-abdominal infections - Zhiqiang Li; Yue Kang; Hongqiang Gao; Yingpeng Zhao; Ding Luo; Dongdong Wang; Xiang Zhang; Jieqi Yu; Guang Chu; Jun Cao; Fan Wang; Xiongqi Zhao; et al. (Infectious Diseases, 2026)

Comprehensive evaluation and analysis of cold tolerance in Neopyropia yezoensis strains based on multiple traits - Zi-Xiang Zhai; Guo-Ying Du; Lan Wu; Lin Tian; Li-Hong Ma (Aquaculture, 2026)

A novel flexible branch-pinecone nanostructured UiO-66-MCA composite nanofiber membrane with bacteriostatic property for effective removal of salicylic acid - Yue Li; Jie Wang; Ping Lin; Shushu Jia; Lijuan Li; Yongxin Li; Ce Wang; Xiang Li (Water Research, 2026)

Nanofibrous core/nanoporous sheath structured ultra–flexible ceramic aerogels for thermal superinsulation - Dizhou Liu; Cong Li; Han Zhao; Hongxuan Yu; Jingran Guo; Shixuan Dang; Duola Wang; Chuanyun Song; Yingde Zhao; Zhengli Yan; Yuanpeng Deng; Jiali Chen; et al. (Science Bulletin, 2026)

Photovoltaic-driven electrochemistry struvite electrolyzer for sustainable phosphate recovery - Weike Lin; Ying Xiang; Xinglong Wu; Chen Xia; Lanlan Zheng; Jin Li; Fang Wang (Process Safety and Environmental Protection, 2026)

Cryo-EM structures of Arabidopsis heteromultimeric isoamylase complex essential for starch granule biogenesis - Ruiying Wang; Wenjuan Li; Yutong Wu; Huajian Lin; Xiang Lin; Lizhi Zhu; Ruiqiang Ye; Jinru Zhang; Minrui Fan (Molecular Plant, 2026)

Photo-responsive imprinted cellulose nanocrystalline aerogels for selective terbium recovery and controlled desorption - Youming Zhu; Xudong Zheng; Jingbo Sun; Lin Guo; Xinmiao Pan; Xiang Gu; Xuan Ma; Jinfeng Mei; Zhongyu Li (Journal of Cleaner Production, 2026)

Multidimensional detection and predictive modeling of Tricholoma matsutake freshness during postharvest storage - Yun Li; Lin Yang; Yahui Zhu; Laizhao Guo; Xiang Wang (Food Research International, 2026)

Promotion of nitric oxide to ammonia via nickel species enhanced active hydrogen generation - Hui Liu; Lin Wu; Yingxue Fu; Zhujiang Wang; Jiaqi Long; Jing Yuan; Xinlei Wang; Jieyu Li; Jun Wu; Kaisong Xiang (Chemical Engineering Journal, 2026)

Ultrasound-sensitized gas vesicles enable spatiotemporal therapeutics of solid tumors - Juanjuan Li; Yong Liu; Xiaoli Jiang; Jiani Han; Yanqiong Tang; Hong Li; Xiang Ma; Xue Chi; Min Lin; Zhu Liu (Chemical Engineering Journal, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Exploring the nonlinear and spatial effects of urban activity heterogeneity on the nighttime thermal environment using machine learning and GWR - Jingyi Lin; Wei Gan; Xiang Li; Xiaochi Xu (Building and Environment, 2026)

Reinforcement Mechanism and Design Method for Geological Defects in Arch Dam Abutments - Peng Lin; Yunfei Xiang; Zichang Li; Haoyang Peng; Yaolai Liu (Rock Mechanics and Rock Engineering, 2026)

ACSL4 Inhibition by AS-252424 Protects Visual Function by Suppressing RGC Ferroptosis After Retinal Ischemia Reperfusion Injury - Keyu Liu; Zihao Lin; Wu Xiang; Jiayi Zhang; Xiaofeng Wu; Chenzhao Ma; Yantao Wei; Jiawei Wang; Jianqiao Li (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Breaking the limitations of scenes and sensors variability: A novel unsupervised domain adaptive instance segmentation framework for agricultural field extraction - Ren Wei; Lin Yang; Xiang Li; Chenxu Zhu; Lei Zhang; Jie Wang; Jie Liu; Liming Zhu; Chenghu Zhou (Remote Sensing of Environment, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

6PPD-Q driven rare and abundant taxa functional partitioning shapes soil ecological response - Xinwei Shi; Weitao Liu; Ruiying Shi; Yichen Ge; Xiang Li; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Dasong Lin; Yuebing Sun (Journal of Hazardous Materials, 2025)

A novel, clean and efficient two-stage leaching process for extracting niobium from clay weathered basaltic crust - Lin Wu; Zhilong Huang; Tao Wu; Zhengzhong Xiang; Taiyi Luo; Lin Ye; Hongpeng Fan; Qingyu Li (Journal of Cleaner Production, 2025)

Biomass-derived activated carbon-supported CuZnOS bimetallic oxysulfide catalyst with highly efficient catalytic reduction of organic and hexavalent chromium pollutants - Jiqing Li; Yuanbo Guo; Kening Xiang; Haoyu Wang; Tao Liu; Cuizhu Li; Zhenjie Wu; Yuhao Hong; Dong-Hau Kuo; Dongfang Lu; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2025)

Photocatalytic of hydrogen peroxide production on chelating agent decorated zinc cadmium sulfide@halloysite hybrid - Sen Lin; Shiyong Sun; Jun Liu; Xiang Li; Haoming Tang; Lin Gong; Xingyun Yang (Journal of Environmental Chemical Engineering, 2025)

Identification of new coumarin-cinnamic acid hybrid FtsZ inhibitors as potential bactericides for enhancing the yield and quality of rice - Ling Zhang; Si-yue Ma; Wan Chen; Lin-li Yang; Yue Ding; Xiang Zhou; Li-wei Liu; Zhi-bing Wu; Song Yang (Food Chemistry, 2025)

Quantitative risk assessment of Listeria monocytogenes in cooked meat products from retail to consumption in China - Xiang Wang; Lisha Liu; Xiao Liu; Yibaina Wang; Yeru Wang; Yan Qi; Shuran Yang; Lin Yan; Dajin Yang; Zhaoping Liu; Jianwen Li; Li Bai (Food Control, 2025)

Construction of 4,5 ′- diaminodibenzo-18-crown-6-grafted graphene cellulose composite aerogel for efficient and selective adsorption of Cs+ from acidic aqueous solution - Lin Guo; Xudong Zheng; Xuan Ma; Xiang Gu; Xinmao Pan; Jinfeng Mei; Zhongyu Li (Environmental Research, 2025)

Mechanical performance of an assembled 3D auxetic hybrid structure under eccentric and axial compression - Jia Shuo Liu; Yi Zhang; Xiang Jie Wei; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Tao Ding; Jia Hui Zhang; Lin Hua; Tong Cheng; Xin Ren (Engineering Structures, 2025)

Dissolving microneedles loaded with Acanthopanax Senticosus-derived vesicles and PEI for antibacterial activity, cfDNA scavenging, anti-inflammation, and angiogenesis in diabetic wounds - Huiling Ye; Junze Tang; Wanting Liang; Yushan Li; Zhaoyi Ye; Jiasen Lin; Guining Cao; Yaoxun Zeng; Yu Sun; Meijing Wang; Ziqiao Li; Xin Cheng; et al. (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

Zinc Fertilizer Application in Different Stages Changes the Accumulation and Remobilization of Zinc in Winter Wheat - Muhammad Fraz Ali; Yuxi Niu; Guoming Li; Lijuan Ma; Xiang Lin; Shubo Gu; Yong Han; Dong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Unraveling the potential mechanism and prognostic value of pentose phosphate pathway in hepatocellular carcinoma: a comprehensive analysis integrating bulk transcriptomics and single-cell sequencing data - Bin Li; Tao Zeng; Cui Chen; Yuankai Wu; Shuying Huang; Jing Deng; Jiahui Pang; Xiang Cai; Yuxi Lin; Yina Sun; Yutian Chong; Xinhua Li; et al. (Functional & Integrative Genomics, 2025)

Gastrodin Attenuates Neuroinflammation and Injury in Young Rats with LiCl/Pilocarpine-Induced Status Epilepticus - Jie Dai; Hai-lin Shen; Jia Li; Yong Zhou; Zheng-xie Dong; Xiang-yang Zhu (Biochemical Genetics, 2025)

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Prevalence and functional impact of the interactions between lysogenic phages and hosts in activated sludge systems: Insights from large-scale metagenomics and experimental evidence - Jie Li; Depeng Wang; Qifeng Zhang; Xiwei He; Peng Liu; Lin Ye; Hongqiang Ren; Xu-Xiang Zhang (Water Research, 2025)

Concentration-dependent visual SO2 detection from trace to pure in a zirconium MOF - Guang-Rui Si; Xiang-Jing Kong; Lin-Hua Xie; You-Tuo Zhang; Tao He; Jian-Rong Li (Science Bulletin, 2025)

Dynamic hyphal specialization remodeling enables Botrytis cinerea to overcome diverse host defenses during infection - Chen Qian; Yuxuan Lin; Chuanxi Zhu; Huan Liu; Junwei Zhao; Xiang Li; Dandan Ren; Jufen Li; Yiwen Wang; Ling Xu; Pinkuan Zhu (Physiological and Molecular Plant Pathology, 2025)

Light-emitting diode-derived blue light overexposure accelerates corneal endothelial cell aging by inducing abnormal ROS accumulation - Zhaolin Liu; Yiran Yang; Ke Yan; Jieli Wu; Xiang Lin; Liying Tang; Qingjian Li; Caihong Huang; Jiaoyue Hu; Zuguo Liu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Advanced membrane technology for per- and polyfluoroalkyl substances removal: Innovations in membrane materials and hybrid systems - Wei Yu; Jiaheng Teng; Xiang Cai; Liguo Shen; Genying Yu; Bisheng Li; Leihong Zhao; Hongjun Lin (Journal of Environmental Management, 2025)

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

Life cycle environmental and economic assessment of co-combustion strategies for raw and landfilled municipal solid waste - Maiwei Chen; Xianchao Xiang; Jie Chen; Yaqi Peng; Jianshan Li; Xiaoqing Lin; Qunxing Huang; Yuqi Jin; Xiaodong Li; Jianhua Yan (Environmental Research, 2025)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

Mechanical properties of waterbomb origami tubes with enhanced energy absorption and crushing efficiency - Xiang Jie Wei; Yi Zhang; Wei Zhong Jiang; Meng Li Xue; Yi Chao Qu; Xiao Ji; Tao Ding; Jia Hui Zhang; Lin Hua; Wei Shen; Xin Ren (Engineering Structures, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Magnesium-enriched biochar as a multifunctional carrier: unlocking productivity and stability in the algal-bacterial symbiosis system - Xiu Zhang; Xiang Cai; Xin Hu; Chenlu Zong; Hongjun Lin; Liguo Shen; Jiaheng Teng; Bisheng Li; Leihong Zhao; Meijia Zhang (Chemical Engineering Journal, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

An innovative and clean strategy to recover copper resources from waste printed circuit boards: Malic acid leaching and micro-nano copper preparation - Xi-guang Li; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Xiao-tian Zhao; Chun-chen Nie; Lin Li; Shuai Yan; Xiang-nan Zhu (Chemical Engineering Journal, 2025)

Smart stimuli-responsive biomaterials for oral and maxillofacial tissue repair and regeneration - Yixuan Jiang; Xingrui Li; Zhuozhen Li; Hanyu Jiang; Bin Wang; Lin Xiang (Chemical Engineering Journal, 2025)

Dual-functional SnO2-SnS2 heterostructure fibers for dendrite-free and catalytically enhanced Zn-I2 batteries - Hanjian Chen; Jiapei Li; Lizhi Xiang; Kunlun Liu; Yicai Pan; Xiaoge Li; Jinmeng Chen; Dewu Lin; Xinyan Li; Shaobo Zhang; Chao Xing; Pan Xue (Chemical Engineering Journal, 2025)

Formation and efficient inhibition of polychlorinated-ρ-dibenzodioxins and dibenzofurans during pyrolytic gasification of rural solid waste: Laboratory, pilot, and full-scale experiments - Xiaoqing Lin; Jiangtao Qian; Yunfeng Ma; Yuxuan Ying; Weican Xiang; Jianhua Yan; Xiaodong Li (Chemical Engineering Journal, 2025)

Orbit determination of GNSS-denied LEO satellites using single inter-satellite link measurements - Xiang Chen; Chengpan Tang; Wujiao Dai; Shanshi Zhou; Lin Pan; Jiarong Zhu; Kai Li; Ziqiang Li (Advances in Space Research, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Simulation of surface water–groundwater interaction in coal mining subsidence areas: A case study of the Kuye River Basin in China - Xiang Li; Song Du; Shihang Hu; Donglin Dong; Dong Jiang; Chenglong Cao; Gang Lin; Jingying Fu (Journal of Hydrology, 2025)

Physical protection by soil aggregates drives carbon gains in mangrove restoration: Evidence from coastal aquaculture ponds - Ning Hou; Xiaolei Yin; Weiqi Wang; Xiang Yang; Yuan Li; Yuanchun Zou; Zhaoliang Song; Shaoying Lin; Zhineng Xiao; Rongbin Yin; Fanjiang Zeng; Zhihao Zhang; et al. (Journal of Environmental Management, 2025)

Oxygen-doped Ag3SbS3 with the hydrophobic-to-hydrophilic transformation for efficient reduction of organic and hexavalent chromium pollutants - Kening Xiang; Haoyu Wang; Tao Liu; Cuizhu Li; Zhengjie Su; Pengkun Zhang; Dong-Hau Kuo; Samuel Ndaghiya Adawara; Dongfang Lu; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Fatigue performance of CFRP-strengthened steel pipes with semi-elliptical surface cracks - Tao Chen; Zhuxuan Li; Xiang-Lin Gu; Zhigang Xiao; Wensu Chen; Haoran Zuo (Engineering Structures, 2025)

Harnessing basic helix-loop-helix-mediated transcriptional reprogramming in mixotrophic Chlorella for synergistic carbon waste remediation and biofuel production - Yu-Feng Yang; Jin-Hua Mou; Yu-Cheng Yang; Lan-Lan Hu; Wen-Li Huang; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2025)

Enzymatic resistance of starch-polyphenol inclusion complexes: polyphenol inhibition and structural changes during in vitro digestion - Haoran Fan; Lin Sun; Xu Yao; Yangyang Wen; Xuesong Xiang; Hongyan Li; Jing Wang; Baoguo Sun (Carbohydrate Polymers, 2025)

A Typical Riedel Shear Pattern of Active Faults in the Laolongwan Basin, Northeastern Tibetan Plateau - Kai-Xun Wang; Xiao-Gang Li; Wei Shi; Xiang-You Feng; Qian Yang; Jie Li; Zheng-Jian Xu; Zhou-Jun Peng; Shao-Hua Xu; Yi-Xue Xiong; Mao Lin (Journal of Earth Science, 2025)

Distribution pattern of cetaceans in the northern South China Sea based on visual surveys and environmental DNA metabarcoding - Shengming Deng; Xiang Zhang; Min Liu; Bai‐An Lin; Yongcan Zhou; Mingming Liu; Wenzhi Lin; Mingli Lin; Lijun Dong; Hui Kang; Binshuai Liu; Shenglan Chen; et al. (Conservation Biology, 2025)
The South China Sea (SCS) is vital habitat and potential nursery and feeding grounds for large cetaceans, such as the sperm whale ( Physeter macrocephalus ), making understanding of the temporal and spatial patterns of cetaceans in this region essential. We examined the accuracy of environmental DNA (eDNA) in detecting cetacean species diversity and determine the spatial and temporal distribution of cetaceans in the northern SCS. We conducted 5 ship‐based visual surveys for cetaceans in 3 summers and 2 springs from 2020 to 2023 and used eDNA metabarcoding to determine the relative abundance and spatial and temporal distribution of cetaceans in offshore and abyssal areas of the northern SCS. We detected 18 cetacean species through visual observations and eDNA metabarcoding. Both methods identified 12 species in common. Cetaceans’ presence varied temporally. We detected 7 species in the springs and 17 species in the summers. Expedition route design, meteorological conditions, and sea conditions between the 2 seasons partly explained the seasonal differences. The species of Ziphiidae, Physeteridae, and Kogiidae tended to occupy regions with high bathymetric drop gradients, particularly those situated on continental slopes and seamounts. The Delphinidae were more widely distributed and relatively more abundant. Of the cetaceans successfully identified by eDNA metabarcoding, species with relatively large group sizes and that were relatively close to the sampling sites tended to be more easily detected. Our results provide new information on the relative abundance and spatial and temporal distribution of cetaceans and indicate that eDNA techniques can provide additional information and serve as a complementary tool for cetacean monitoring and conservation.

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

Distribution characteristics and formation mechanisms of PCDD/Fs during pyrolysis and gasification of municipal solid waste - Xiaoqing Lin; Jiangtao Qian; Yuxuan Ying; Weican Xiang; Yunfeng Ma; Jianhua Yan; Xiaodong Li (Waste Management, 2025)

Shift to intra-EU-OECD trade enhanced environmental benefits after Basel Convention Plastic Waste Amendments - Kai Li; Hauke Ward; Hai Xiang Lin; Arnold Tukker (Resources, Conservation and Recycling, 2025)

Knockout of SlCBF1 enhances tomato fruit resistance against Botrytis cinerea after chilling stress treatment - Lanting Xiang; Yujing Li; Pan Shu; Jiping Sheng; Lin Shen (Postharvest Biology and Technology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Dissolved organic matter-mediated metabolic shifts in Chlorella sorokiniana enhanced bioremediation of multi-ionic stress - Ting-Bin Hao; Zhong-Hong Zhang; Lan-Lan Hu; Si-Fen Liu; Jin-Hua Mou; Peizeng Yang; Zhiguo Yuan; Qi Zhang; Srinivasan Balamurugan; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; et al. (Journal of Hazardous Materials, 2025)

Occurrence, removal and ecological risk assessment of antibiotics in rural domestic wastewater treatment systems in the Beijing-Tianjin-Hebei region - Hongliang Wang; Sai Zhang; Ziyu Lin; Feifei Xiao; Bao Xiang; Ao Li (Journal of Hazardous Materials, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Geochemical mapping and distribution patterns of critical elements resources in Chinese coal-bearing strata - Ruiwen Yan; Jun Zhu; Qingyi Cao; Gang Lin; Xiang Li; Furui Xi (International Journal of Coal Geology, 2025)

Primary colorectal cancer cells cultured in hydrogel microcapsules-integrated microfluidic chip for chemotherapy evaluation - Chuanmeng Pan; Xiang Lin; Feika Bian; Liqun Li; Xian Shen (Chemical Engineering Journal, 2025)

A rapid and efficient microenvironment improving hyaluronic acid microneedle dressing for burn wound synergistic treatment - Lin Lei; Wei Li; Jiajia Wang; Qi Liu; Feng Zeng; Yunqiang Xiang; Xinyuan Fu; Rui Tao; Zhangyou Yang (Carbohydrate Polymers, 2025)

Investigating the Impact of Drought During Returning Green and Jointing Stages on Different Tillers Position of Winter Wheat - Muhammad Fraz Ali; Ping Li; Lijuan Ma; Changjie Feng; Shubo Gu; Xiang Lin; Dong Wang (Journal of Plant Growth Regulation, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Xanthine oxidase inhibitory constituents from the roots of Ampelopsis japonica - Yu-Lin Li; Fen Liu; Li-Yun Zhao; Han-Xiang Li; Aikebaier Jumai; Zhi-Fang Xu; Sheng-Xiang Qiu (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Metabolomics unravels the formation pathway of advanced glycation end products in preserved egg yolk mediated by OH− during pickling - Le Chen; Zhuosi Yu; Shiqin Dong; Yiqun Huang; Xiaole Xiang; Yu He; Shugang Li; Lin Ye (Food Chemistry, 2025)

Improved Stability of Aerobic Granular Sludge Under Low Hydraulic Shear Force by Adding Magnetic Modified Low Expansion Vermiculite as Nucleating Agent - Wenjuan Xiang; Yuan Gao; Jie Xu; Xuejun Bi; Lin Li; Shu Chen (Water, Air, & Soil Pollution, 2025)

Soil comammox Nitrospira dominates over ammonia-oxidizing archaea and bacteria in the invasion of Solidago canadensis - Wen-Tao Qiao; Yong-Feng Wang; Xue-Yan Hou; Xiang-Zhen Li; Dao-Lin Du; Zhi-Cong Dai; Guang-Qian Ren; Xiao-Jun Zheng; Chao-Ying Liu (Plant and Soil, 2025)

Improving grain yield in crop/forage intercropping systems by altering forage cutting date - Fangru Wan; Lin Xiang; Guanrong Dai; Xiaozheng Wang; Jiena Li; Yinjuan Li; Baoqing Zhang; Longshuai Ma (Plant and Soil, 2025)

Genesis of the South Pit Deposit in Jiama District, Tibet: Constraints from Geology, Geochronology and Amphibole Geochemistry - Pan Tang; Juxing Tang; Bin Lin; Aorigele Zhou; Faqiao Li; Xiang Fang; Jing Qi; Mengdie Wang; Yan Xiong; Yuke Xie; Zhengkun Yang; Xiaofeng Yao (Journal of Earth Science, 2025)

Regulating the Cu-Ce interaction of CuCeOx/SAPO-34 catalysts to achieve a wide reaction temperature window for the collaborative synergistic removal of NOx and toluene at low temperatures and reaction mechanisms - Rong Liu; Xuehui Jia; Lin Li; Fengying Li; Xiang Tu; Weicheng Xu; Hansun Fang; Danping Li; Hong Huang; Chenglong Yu (Journal of Hazardous Materials, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Potato starch/sodium alginate composite film containing lycopene microcapsules for extending blueberry shelf life - Xu Li; Jiayi Wu; Lulu Hu; Wenliang Xiang; Zhiwei Chen; Ying Meng; Lin Yang (Food Packaging and Shelf Life, 2025)

A redox-modulating coating with multi-enzyme activity on engineered nanoparticles: An effective strategy for enhancing the control of plant bacterial diseases - Zhenghao Ding; Liwei Liu; Qingqing Song; Lin Chen; Guangdi Wang; Hong Li; Xinxin Tuo; Zhibing Wu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2025)

Genomic analysis of the novel Stenotrophomonas phage vB_Srh_LBjhp91a, isolated from a Karst cave in China - Lou Ren; Zheng Fang; Shixia Li; Qingshan Wu; Lan Xiang; Chuangen Lin; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2025)

A Novel Metric for Assessing Long-Term Outcomes in Adults with Chiari Malformation Type I: Occipitocervical Dura Angulation (ODA)—Applications and Value - Bo Wang; Shi-Chao Chen; Yao-Wu Zhang; Wei-Hao Liu; Chong Wang; Yi-Xiang Liu; Guang-Hao Zheng; Jia-Lin Li; Kai Ji; Jun Yang; Yong-Zhi Wang; Wen-Qing Jia (The Cerebellum, 2025)

The substrate configuration influences pollutant removal in constructed wetlands: From the aspects of submerged status of substrate and carbon-felt distribution - Xiang-Zheng Li; Tong Wang; Ting Yang; Xue Li; Lin-Wei Wu; Lin-Lan Zhuang; Jian Zhang (Water Research, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Fe/S co-doped BiOCl sulfur-oxychloride for efficient catalytic reduction of organic and Cr6+: Synergistic regulation of heterovalent states and oxygen vacancy defects - Cuizhu Li; Haoyu Wang; Tao Liu; Pengkun Zhang; Qiong Li; Kening Xiang; Dong-Hau Kuo; Dongfang Lu; Mengistu Tadesse Mosisa; Yiqiang Liao; Jinguo Lin; Xiaoyun Chen (Journal of Water Process Engineering, 2025)

Low-dose tire wear chemical 6PPD-Q exposure elicit fatty liver via promoting fatty acid biosynthesis in ICR mice - Lili Wang; Weitian Tang; Nan Sun; Jia Lv; Jiayue Hu; Lin Tao; Cheng Zhang; Hua Wang; Li Chen; De-Xiang Xu; Yihao Zhang; Yichao Huang (Journal of Hazardous Materials, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Insights into effects of processing and food matrices on structure and ELISA detection of sarcoplasmic calcium binding protein - Wenye Zhu; Qingwen Liu; Yuhao Huang; Hao Wang; Hang Lin; Xiang Gao; Hong Lin; Zhenxing Li (Food Chemistry, 2025)

Elucidating the interaction mechanism of rutin with β-casein and β-lactoglobulin: A comprehensive analysis using multi-spectroscopy, molecular docking, and molecular dynamic simulations - Hailin Wang; Leiwen Xiang; Zhuangwei Zhang; Guoqiang Li; Peng Li; Wentao Chen; Yu Fang; Xinyan Lin; Shufen Lin (Food Chemistry, 2025)

Target-mediated rolling circle amplification/transcription coupling with double signal amplification of exonuclease III-assisth most of them are low-ed CRISPR/Cas12a-Cas13a for simultaneously ultrasensitive detection of aflatoxin B1 and ochratoxin A - Yaqi Li; Qingyue Sun; Xin Chen; Yian Jian; Siye Wei; Xiang Zuo; Chang Liu; Dezhao Kong; Feng Lin (Food Control, 2025)

Enhancing anaerobic digestion of sludge with dual-heteroatom-doped biochar derived from digested sludge: In-situ reuse of anaerobic residues for system self-circulation - Shengye Duan; Junguo He; Yijie Zhong; Lin Li; Xiang Zou; Qiupeng Cai; Ruimiao Zhang; Xinxin Cui; Yuanyi Zhao; Yunlong Liu; Jie Zhang (Environmental Research, 2025)

An ultrafast dual-channel ratiometric fluorescence probe based on functionalized N-GQDs for dynamic monitoring of salicylic acid in plants - Hou-Yun Huang; A-ling Tang; Feng Gao; Shuai Tan; Zhi-Min Rao; Li-Wei Liu; Shi-Tao Liu; Xiang Zhou; Lin-Lin Yang; Song Yang (Chemical Engineering Journal, 2025)

Defect engineering of Z-scheme heterojunction catalysts for efficient CO2 photoreduction - Ye Song; Yang Song; Xiang Li; Ruoyu Wang; Shangcong Sun; Qiuqiao Jiang; Haitao Song; Wei Lin; Wenbin Lin (Chemical Engineering Journal, 2025)

Potential links between the progress in environmental governance and the prevalence of mental disorder burden: New insight from a dynamic panel-data analysis for 197 countries - Jun-Yan Xi; Li-Chang Chen; Xue-Qi Li; Jie Hu; Wei Hu; Jian-Jun Bai; Yi-Ning Xiang; Yu-Can Zhang; Jia-Jia Wang; Shi-Hao Wang; Jing Gu; Yuan-Tao Hao; et al. (Sustainable Cities and Society, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Study on the nitrogen migration of different biomass by activated carbon-based MOF catalyst in hydrothermal environment - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Lin-yu Zhang; Zhi Yang; Fu-xiang Yang (Fuel, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Simultaneous removal of heavy metals and antibiotics from anaerobically digested swine wastewater via functionalized covalent organic frameworks - Yupei Zhang; Shuai Zhang; Yan Lin; Shaohua Wu; Xiang Li; Chunping Yang (Environmental Research, 2025)

Membrane fouling behaviors of microplastic in coagulation-ultrafiltration process: Role of surface functional groups - Yue Shen; Tao Jian; Genying Yu; Hongjun Lin; Xiang Cai; Liguo Shen; Zengjian Zhao; Leihong Zhao; Meijia Zhang; Die Ling Zhao; Bisheng Li (Chemical Engineering Journal, 2025)

Oxygen-vacancy-rich Ni/CeO2: UiO-66-derived high-efficiency catalyst for low-temperature CO2 methanation - Yidan Li; Yahui Yang; Zhenzhen Huang; Huilin Zhou; Riying Zeng; Xiaohan Lin; Xiuling Ma; Lihua Wang; Shengchang Xiang; Zhangjing Zhang (Chemical Engineering Journal, 2025)

Perovskite quantum dots Revolutionize Lithium-Sulfur battery Performance: Cathode catalytic Breakthrough with CsPbBr3 - Renjing Duan; Xiaoshi Lang; Xiang Wang; Lan Li; Tingting Qu; Lin Wang; Jianbin Li; Chuangang Yao; Kedi Cai (Chemical Engineering Journal, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Glycerol-driven optimization of algae-bacteria symbiosis systems for enhanced lipid production and self-flocculation - Yuwei Zhang; Jiaheng Teng; Jiahui Huang; Liguo Shen; Hongjun Lin; Renjie Li; Xiang Cai; Zeqiong Xu; Meijia Zhang (Journal of Environmental Chemical Engineering, 2025)

Two-stage inoculation with lignocellulose-degrading microorganisms in composting: Enhanced humification efficiency and underlying mechanisms - Yu Zhang; Binfeng Lin; Yuhao Hao; Mengling Lu; De Ding; Shiyuan Niu; Hongquan Xiang; Zhi Huang; Jianbin Li (Environmental Research, 2025)

Ultra-high temperature and salinity resistant microspheres featuring “Rigid hydrophobic core- soft hydrophilic Shell” structure for deep reservoir profile control - Wei Xiang; Lin Li; Yunbo Dong; Zizhao Wang; Zifan Song; Mingwei Zhao; Caili Dai (Chemical Engineering Journal, 2025)

Uncovering somatic genetic drivers in prostate cancer through comprehensive genome-wide analysis - Lede Lin; Zhen Li; Kai Chen; Yanxiang Shao; Xiang Li (GeroScience, 2025)

The effects of phospholipids (PL) addition in the high fat diet on growth performance, oxidative stress, lipid and protein metabolism, and muscle development in yellow catfish Pelteobagrus fulvidraco - Qing-Lin Li; Biao Wang; Hua Zheng; Li-Xiang Wu; Peng-Cheng Xu; Xiao-Ying Tan (Aquaculture, 2025)

CAR-NK cell therapy: a potential antiviral platform - Ming-Hao Lin; Li-Juan Hu; Jeffrey S. Miller; Xiao-Jun Huang; Xiang-Yu Zhao (Science Bulletin, 2025)

Performances and mechanisms of catalytic ozonation for paint wastewater via catalysts of Fe-Mn deposited within graphitized beads of γ-Al2O3 - Mei Dai; Chunping Yang; Liusiyu Yang; Yan Lin; Shanying He; Xiang Li; Qiuya Niu; Shaohua Wu (Journal of Cleaner Production, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Element Redistribution and Age Resetting in Shock-Deformed Zircon from the Chicxulub Impact Structure - Jiawei Zhao; Long Xiao; Zhiyong Xiao; Xiang Wu; Qi He; Jialong Hao; Ruiying Li; Yangting Lin (Geochimica et Cosmochimica Acta, 2025)

The mechanism of egg white protein to enhance the thermal gel properties of giant squid (Dosidicus gigas) surimi - Fuge Niu; Xiang Li; Chenyang Lin; Xinyu Hu; Bin Zhang; Weichun Pan (Food Chemistry, 2025)

Layered nitrogen fertilization regulates root morphology to promote synergistic nitrogen and phosphorus absorption in maize (Zea mays L.) - Changhong Liu; Shengyan Pang; Xiufeng Li; Pei Liu; Yang Zhou; Xiang Lin; Shubo Gu; Dong Wang (Field Crops Research, 2025)

Moderate deep banding of phosphorus enhanced winter wheat yield and fertilizer uptake efficiency by promoting nutrient absorption and translocation of pre-anthesis nutrient - Yang Zhou; Zhenyan Li; Yongqiang Li; Jinwei Li; Ruoling Ma; Xiang Lin; Shubo Gu; Jing Yang; Dong Wang (Field Crops Research, 2025)

Efficacy and application potential of purified hydrocolloid coatings sprayed onto maize seeds subjected to anti-aging - Lin Zhang; Shi-Chao Yuan; Tai-Yue Wang; Xiang-Yang Wang; Xiao-Di Hao; Li-Ting Hao; Chen Shi (Environmental Research, 2025)

Insights into nitrogen metabolism and humification process in aerobic composting facilitated by microbial inoculation - Binfeng Lin; Yu Zhang; Yuhao Hao; Mengling Lu; Hongquan Xiang; De Ding; Shiyuan Niu; Kai Li; Jianbin Li; Zhi Huang (Environmental Research, 2025)

Microbial synergy mechanism of hydrogen flux influence on hydrogen-based partial denitrification coupled with anammox in a membrane biofilm reactor - Si Pang; Xiang Cai; Lin Yang; Jingzhou Zhou; Xiaodi Li; Siqing Xia (Environmental Research, 2025)

Identification of novel biomarkers for atherosclerosis using single-cell RNA sequencing and machine learning - Xi Yong; Tengyao Kang; Mingzhu Li; Sixuan Li; Xiang Yan; Jiuxin Li; Jie Lin; Bo Lu; Jianghua Zheng; Zhengmin Xu; Qin Yang; Jingdong Li (Mammalian Genome, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Impacts of chitosan/pullulan/carvacrol film on the quality and microbial diversity of refrigerated goat meat - Longquan Xiao; Molazi Lapu; Lin Cui; Jing Li; Xinhui Wang; Xiang Li; Mingxue Liu; Dayu Liu (Meat Science, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Differential contribution of Cu2+ and OH− to the formation of Nε-carboxymethyllysine and Nε-carboxyethyllysine in preserved egg white during pickling - Le Chen; Zhuosi Yu; Shiqin Dong; Zixiao Li; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

Inhibitory effect of L-arginine on the oxidative aggregation behavior of myofibrillar proteins in the Antarctic krill (Euphausia superba): pH and antioxidation - Xinyu Zhang; Xiang Ren; Junxin Lin; Peizi Sun; Yuting Tan; Dongmei Li (Food Chemistry, 2025)

Vitamin C encapsulated biomimetic nanogels with macrophage membrane decoration for chronic wound healing - Xin Yang; Xiang Lin; Jinbo Li; Tapani Viitala; Yuanjin Zhao; Hongbo Zhang; Luoran Shang (Chemical Engineering Journal, 2025)

Evaluating Damage Growth and Outburst Trend During Gas Drainage Under Coupled Microstructure-Multi-field Behaviour - Dayu Ye; Guannan Liu; Xiang Lin; Hu Liu; Danqi Li (Rock Mechanics and Rock Engineering, 2025)

The influence of atmospheric turbulence-induced optical intensity scintillation on the accuracy of satellite-to-ground laser one-way timing - Zhiqian Yin; Xin Zhou; Lin Lu; Chuanbo Zhang; Peng Xiang; Weiheng Dai; Yuliang Chen; Tao Fang; Zizhuo Li; Zhuoying Wang; Jiaqiang Nie; Xiangfei Chen (Advances in Space Research, 2025)

Soil legacies of genotypic diversity enhance population resistance to water stress - Zekang Liu; Cai Cheng; Qun Zhang; Xing Tian; Lin Jiang; Kerri M. Crawford; Xiang Liu; Jianquan Liu; Qiang He; Bo Li; Jihua Wu (Ecology, 2025)
While the positive relationship between plant diversity and ecosystem functioning is frequently observed and often attributed to direct plant–plant interactions, it remains unclear whether and how the effects of plant diversity endure through soil legacy effects, particularly at the level of genotypic diversity. We manipulated the genotypic diversity of Scirpus mariqueter and tested its soil legacy effects on a conspecific phytometer under low‐ and high‐water availability conditions. We found that genotypic diversity enhanced phytometer productivity through soil legacies, with stronger effects under low‐water availability conditions, improving its resistance to water stress. Moreover, this effect was attributed to the association between asexual and sexual reproductive strategies by increasing ramet number to ensure plant survival under low‐water availability and promoting sexual reproduction to escape stress. The observed diversity effects were primarily associated with increased levels of microbial biomass in soils trained by populations with diverse genotypes. Our findings highlight the importance of plant genotypic diversity in modulating ecosystem functioning through soil legacies and call for management measures that promote genetic diversity to make ecosystems sustainable in the face of climate change.

Concentration-dependent effect of norfloxacin on iron toxicity in the intestine of large yellow croaker Larimichthys crocea (Richardson, 1846) - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Bin Liu; Min-Hui Yu; Hui Zhang; Fei Li (Frontiers in Marine Science, 2025)
This study explores the effects of norfloxacin (NOR) on oxidative damage, iron (Fe) transport, energy metabolism, and immunotoxicity in the intestine of large yellow croaker under Fe stress. The fish were subjected to Fe (180 μg/L), low-dose NOR (1.8 μg/L, LNOR), high-dose NOR (180 μg/L, HNOR), Fe plus LNOR, and Fe plus HNOR for 60 days. These results demonstrated that Fe alone exposure increased malondialdehyde (MDA), protein carboxylation (PC), and mortality rate, and impaired intestinal tissue, which was related to the increment of Fe accumulation. Compared to Fe alone exposure, Fe plus LNOR exposure decreased MDA, PC, and mortality rate, and alleviated intestinal malformations by improving Fe transport, energy metabolism, anti-inflammatory response, and protein folding protective effect, and reducing pro-inflammatory response, indicating that LNOR had an antagonistic effect on Fe toxicity. Compared to Fe alone exposure, Fe plus HNOR exposure elevated MDA, PC, and mortality rate, and deteriorated intestinal malformations by inhibiting Fe excretion, energy metabolism, anti-inflammatory response, and protein folding protective effect, and enhancing pro-inflammatory response, indicating a synergetic effect between HNOR and Fe stress. These findings suggested that NOR had a dose-dependent effect on Fe-toxicity to large yellow croaker, which contributes to revealing the molecular mechanisms behind their interaction and its ecological implications.

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Crop diversity significantly enhances soil carbon sequestration via alleviating soil inorganic carbon decline caused by rhizobium inoculation - Chuan-Lin Xiao; Nai-Hao Ji; Ping Wang; Jing-Ru He; Xiang Wang; Long Li (Soil and Tillage Research, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Review of vibration induced by gas-liquid two-phase flow inside pipes - Lin Ding; Yitong Fu; Xiang Li; Jingyu Ran (Ocean Engineering, 2025)

Factors of microbial degradation of organic pollutants: Two meta-analyses - Shibin Liu; Li Guo; Chunyu Xiang; Bowei Zhu; Wenbin Huang; Lin Tian; Jiancheng Tang; Zhanpeng Dai; Ekaterina Filimonenko; Ramzi Mekhalif; Hanzhong Jia; Yakov Kuzyakov (Journal of Cleaner Production, 2025)

Priority sources identification and risks assessment of heavy metal(loid)s in agricultural soils of a typical antimony mining watershed - Lianhua Liu; You Li; Xiang Gu; Roberto Xavier Supe Tulcan; Lingling Yan; Chunye Lin; Junting Pan (Journal of Environmental Sciences, 2025)

Human settlement and destructive activities disrupt the positive contribution of dust to plant biomass growth over the past 2000 years - Lin Chen; Youliang Huang; Menghan Qiu; Zhilun Li; Rui Yang; Mengjing Li; Huiling Sun; Lixiong Xiang; Shanjia Zhang; Xiaozhong Huang; Aifeng Zhou (Global and Planetary Change, 2025)

The change rule of lipid oxidation and hydrolysis driven via water in Antarctic krill oil: Based on association colloid formation - Xue-Chen Pei; Xiang-Bo Zeng; De-Yang Li; Xin-Miao Wang; Fa-Wen Yin; Hui-Lin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Transparent mechanism of salted egg (white) hierarchically and synergistically driven by NaCl, NaOH and thermal treatment: Based on empirical data and molecular simulation - Le Chen; Shiqin Dong; Peng Xu; Zhuosi Yu; Yating He; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

In-situ forming flame-retardant gel polymer electrolyte through Ritter reaction: An innovative strategy for enhancing the safety of lithium metal battery - Si-Xin Jia; Tian-Qi Xiang; Zi-Han Zhang; Jian-Jun Zhou; Lin Li (Chemical Engineering Journal, 2025)

Poly[nitrilo(diphenoxyphosphoranylidyne)] passivated MAPbI3 film achieves 21.36% efficiency and superior multivariate stability for air-processed perovskite solar cells - Pengyun Zhang; Xiang Mi; Qi-Lin Lu; Xiangshun Li; Yonggui Li; Huizhen Ke; Jie Xiong (Chemical Engineering Journal, 2025)

Exploring the mechanism of ursolic acid in preventing liver fibrosis and improving intestinal microbiota based on NOX2/NLRP3 inflammasome signaling pathway - Qi Liu; Lin-Xiang Liu; Bi-Min Li; Wang Zhang; Yue Zhang; Peng Chen; Chen-Kai Huang; Yuan Nie; Xuan Zhu (Chemico-Biological Interactions, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

Protein Phosphatase 2ACα Regulates ATR-Mediated Endogenous DNA Damage Response Against Microcephaly - Lin Lin; Jing Ding; Simeng Liu; Chunying Liu; Qing Li; Xiang Gao; Yamei Niu; Wei-Min Tong (Molecular Neurobiology, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

MAT2A is essential for zygotic genome activation by maintaining of histone methylation in porcine embryos - Xiao-Han Li; Song-Hee Lee; Qin-Yue Lu; Cheng-Lin Zhan; Gyu-Hyun Lee; Ji-Dam Kim; Jae-Min Sim; Hyeon-Ji Song; Xiang-Shun Cui (Theriogenology, 2024)

Influence of habitat utilization strategies on trace element signatures in egg contents of green turtles nesting on Xisha Islands, South China Sea - Li Jian; Xiang Li; Xiaobo Zheng; Jingyue Peng; Ting Zhang; Liu Lin; Jichao Wang (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Performance enhancement of floating raft system by exploiting geometric nonlinearity and motion constraint in vibration isolators - Wei Dai; Tianyun Li; Lin Wang; Xiang Zhu; Baiyang Shi; Jian Yang (Ocean Engineering, 2024)

The improvement of gel properties and volatiles for frozen egg white melted assisted with ultrasound - Xiaole Xiang; Shiqin Dong; Le Chen; Yongle Liu; Yingqun Wu; Meijuan Yu; Gan Hu; Shugang Li; Lin Ye (Food Research International, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Specific detection of crustacean allergens in food: Development of indirect competitive and sandwich ELISA targeting sarcoplasmic calcium binding protein - Wenye Zhu; Zhihui Qin; Yuhao Huang; Qi Fu; Hao Wang; Ziye Zhang; Xiang Gao; Yinghui Liu; Hong Lin; Zhenxing Li (Food Bioscience, 2024)

The roles of organic amendments and plant treatments in soil polychlorinated biphenyl dissipation under oxic and sequential anoxic–oxic conditions - Meng Yan; Tingting Peng; Ling Zhao; Qigang Li; Ruini Wu; Yiming Wang; Yucheng Wu; Ying Teng; Xingjia Xiang; Jun Zeng; Xiangui Lin (Environmental Research, 2024)

Riparian restoration in sandy zones with alfalfa as pioneer plant in initial stage of soil and water bioengineering - Lin Yang; Lina Cao; Ting Cao; Hongyong Xiang; Chunguang He; Jia Li; Xiaoyue Zhang; Sayramgul Abu Dumusa; Yu Leng (Ecological Engineering, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Efficient genome engineering in Mycolicibacterium neoaurum using Cas9 from Streptococcus thermophilus - Gedan Xiang; Tao Liu; Lekai Li; Guihong Lin; Ke Liu; Fengqing Wang (Biotechnology Letters, 2024)

Effects of core soil microbial taxa on soil carbon source utilization under different long-term fertilization treatments in Ultisol - Haoran Mao; Guilong Li; Ke Leng; Luyuan Sun; Kailou Liu; Yongxin Lin; Jia Liu; Xingjia Xiang (Soil Ecology Letters, 2024)

Novel Pathogenic Mutation of P209L in TRPC6 Gene Causes Adult Focal Segmental Glomerulosclerosis - Tianxi Yu; Yongqiang Ji; Xin Cui; Ning Liang; Shuang Wu; Chongjun Xiang; Yue Li; Huiying Tao; Yaqi Xie; Hongwei Zuo; Wenting Wang; Nauman Khan; et al. (Biochemical Genetics, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Effects of dietary vitamin D3 and carbohydrate levels on growth performance, carbohydrate metabolism, and intestinal health of yellow catfish (Pelteobagrus fulvidraco) - Li-Xiang Wu; Qing-Lin Li; Zhi Luo; Mette Sorensen; Xiao-Lei Wei; Hua-Jun Zhang; Xiao-Ying Tan (Aquaculture, 2024)

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Super-large diameter slurry shield tunnel encountering boulder formation: Detection, treatment and data analysis - Wei-Hong Yang; Dong Su; Xing-Tao Lin; Zhi-Jia Lv; Zhan-Hu Yao; Hui Li; Ya-Zhou Zhang; Xiang-Sheng Chen (Transportation Geotechnics, 2024)

Wogonin induces mitochondrial apoptosis and synergizes with venetoclax in diffuse large B-cell lymphoma - Ye Lin; Xia Jiang; Mengting Zhao; Youhong Li; Lili Jin; Sumeng Xiang; Renzhi Pei; Ying Lu; Lei Jiang (Toxicology and Applied Pharmacology, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Research on simulation model of deepwater drilling and optimization method of drilling parameters based on energy - Ming Xiang; Bin Li; Yingming He; Zhiqiang Lin; Weiguo Hai; Jin Wang; Qilong Xue (Ocean Engineering, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Corrigendum to “Raman-guided exploration of placental microplastic exposure: Unraveling the polymeric tapestry and assessing developmental implications” [J Hazard Mater 477 (2024) 135271] - Xiang Yun; Liyang Liang; Jiaqi Tian; Ning Li; Zhen Chen; Yongfei Zheng; Shuyin Duan; Lin Zhang (Journal of Hazardous Materials, 2024)

Performance of carbon felt as cathodes in magnesium corrosion method to recover phosphate from swine wastewater - Ying Xiang; Weike Lin; Jinfeng Wei; Fan Yang; Meng Guo; Can Li; Jin Li; Fang Wang (Journal of Environmental Management, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Targeted metabolomics reveals the contribution of degradation and oxidation of lipids and proteins mediated by pH to the formation of characteristic volatiles in preserved egg yolk during pickling - Xiaole Xiang; Le Chen; Shiqin Dong; Zixiao Li; Yongle Liu; Yingqun Wu; Shugang Li; Lin Ye (Food Research International, 2024)

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Automated counting and classifying Daphnia magna using machine vision - Yang Ma; Wenping Xiao; Jinguo Wang; Xiang Kuang; Rongqin Mo; Yanfang He; Jianfeng Feng; Hengling Wei; Liwen Zheng; Yufei Li; Peixin Liu; Hao He; et al. (Aquatic Toxicology, 2024)

TEMDI: A Temporal Enhanced Multisource Data Integration model for accurate PM2.5 concentration forecasting - Ke Ren; Kangxu Chen; Chengyao Jin; Xiang Li; Yangxin Yu; Yiming Lin (Atmospheric Pollution Research, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

A streamlined method to generate endothelial cells from human pluripotent stem cells via transient doxycycline-inducible ETV2 activation - Allen Chilun Luo; Jiuhai Wang; Kai Wang; Yonglin Zhu; Liyan Gong; Umji Lee; Xiang Li; Daniel M. Tremmel; Ruei-Zeng Lin; Donald E. Ingber; James Gorman; Juan M. Melero-Martin (Angiogenesis, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

MOF-derived carbon supporting tubular In2O3 for efficient photocatalytic degradation of antibiotics - Yilin Pan; Kaizhou Huang; Beijia Lin; Xiang Li; Chun Hu; Zhihong Chen; Peng Zhang (Journal of Environmental Chemical Engineering, 2024)

Study on synergistic effect of carrier combined with micro-aeration on anaerobic digestion of food waste - Keke Ding; Baocun Wu; Yi Wang; Linji Xu; Miao Liu; Jinjing Xiang; Yongdong Chen; Li Gu; Jinze Li; Lin Li; Qiang He; Shaowu Liu (Chemical Engineering Journal, 2024)

Role of polarized and interfacial built-in electric fields in photocatalysts for enhanced photocatalytic performance - Caiyu Luo; Chunping Yang; Jun Xie; Xiang Li; Yan Lin; Shehua Tong; Shanying He (Chemical Engineering Journal, 2024)

Large-area and high-efficiency carbon nanotube/silicon heterojunction solar cells enabled by self-similar fiber electrodes and solid-state gel electrolytes - Xian-Gang Hu; Bingsheng Li; Yi-Ming Zhao; An-Ping Wu; Zhenhua Lin; Peng-Xiang Hou; Chang Liu; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Oxygen evolution reaction enhancing electrochemical performance of V-doped Ni(OH)2 for aqueous asymmetric supercapacitors - Ting Xiao; Hongxiang Lin; Can Tang; Xiuru Li; Yuting Mei; Lin Gao; Lihua Jiang; Peng Xiang; Shibing Ni; Yequan Xiao; Xinyu Tan (Chemical Engineering Journal, 2024)

A tetrahedral framework nucleic acids-based gene therapeutic nanococktail alleviates cartilage damage and protects against osteoarthritis progression - Liwei Fu; Jiang Wu; Sirong Shi; Zhichao Zhang; Yazhe Zheng; Pinxue Li; Xun Yuan; Zhengang Ding; Chao Ning; Xiang Sui; Shuyun Liu; Quanyi Guo; et al. (Chemical Engineering Journal, 2024)

Bacterial functions are main driving factors on paddy soil organic carbon in both surface soil and subsoil - Xiang-Wen Huang; Jia-Jun Lin; De-Jin Li; Xiang-Qi Huang; Qi-Huan Xie; Sheng-Gang Pan; Xiang-Ru Tang; Jian-Ying Qi (Agriculture, Ecosystems & Environment, 2024)

Comparative study of atmospheric brown carbon at Shanghai and the East China Sea: Molecular characterization and optical properties - Dongmei Cai; Chunlin Li; Jingxin Lin; Wenwen Sun; Miaomiao Zhang; Tao Wang; Munila Abudumutailifu; Yan Lyu; Xiaojuan Huang; Xiang Li; Jianmin Chen (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Monoterpene-chalcone conjugates and diarylheptanoids isolated from the seeds of Alpinia katsumadai Hayata with cytotoxic activity - Hua-Lin You; Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Xiang-Chun Shen; Nen-Ling Zhang (Phytochemistry, 2024)

Raman-guided exploration of placental microplastic exposure: Unraveling the polymeric tapestry and assessing developmental implications - Xiang Yun; Liyang Liang; Jiaqi Tian; Ning Li; Zhen Chen; Yongfei Zheng; Shuyin Duan; Lin Zhang (Journal of Hazardous Materials, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Hierarchical supramolecules composed of starch-based nanocluster aggregates with light-responsive mechanical strain for remotely rapid and precise actuation - Fu-Xiang Wei; Xu Yuan; Feng-Qiong Jiang; Zhen Wang; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Carbohydrate Polymers, 2024)

Important role of Bacillus subtilis as a probiotic and vaccine carrier in animal health maintenance - Chunmei Yuan; Xiang Ji; Yuyu Zhang; Xinli Liu; Luogang Ding; Jianda Li; Sufang Ren; Fei Liu; Zhi Chen; Lin Zhang; Wenxing Zhu; Jiang Yu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Effect of environmental exposome and influenza infection on febrile seizure in children over 22 years: a time series analysis - Xiaoting Jiang; Conglu Li; Qianying Yue; Yuchen Wei; Yawen Wang; Xiang Qian Lao; Guozhang Lin; Ka Chun Chong (International Journal of Biometeorology, 2024)
Febrile seizures are convulsions predominately occurring in young children. The effects of various exposomes, including influenza infection and external environmental factors, on febrile seizures have not been well-studied. In this study, we elucidated the relationships between ambient temperature, air pollutants, influenza infection, and febrile seizures using 22-year territory-wide hospitalization data in Hong Kong. The aggregated data were matched with the meteorological records and air pollutant concentrations. All-type and type-specific influenza-like illness positive (ILI+) rates were used as proxies for influenza activity. Distributed lag non-linear model in conjunction with the quasi-poisson generalized additive model was used to examine the associations of interest. According to the results, all-type influenza infections were significantly associated with an increased risk of hospital admissions for febrile seizures (cumulative adjusted relative risk [ARR] = 1.59 at 95th percentile vs. 0; 95% CI, 1.51–1.68). The effect of ILI + A/H3N2 on febrile seizure was more pronounced than other type-specific ILI + rates. A low mean ambient temperature was identified as a significant risk factor for febrile seizures (cumulative ARR = 1.50 at 5th percentile vs. median; 95% CI, 1.35–1.66), while the redox-weighted oxidant capacity and sulfur dioxide were not associated with febrile seizures. In conclusion, our study underscores that influenza infections and exposure to cold conditions were related to an increased risk of febrile seizures in children. Thus, we advocate for influenza vaccination before the onset of the cold season for children to mitigate the burden of febrile seizures.

DOTAD: A Database of Therapeutic Antibody Developability - Wenzhen Li; Hongyan Lin; Ziru Huang; Shiyang Xie; Yuwei Zhou; Rong Gong; Qianhu Jiang; ChangCheng Xiang; Jian Huang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Correction: Large yellow croaker (Larimichthys crocea) mitofusin 2 inhibits type I IFN responses by degrading MAVS via enhanced K48-linked ubiquitination - Wen-Xing Li; Xiao-Hong Wang; Yi-Jun Lin; Yuan-Yuan Zhou; Jun Li; Xiang-Yang Zhang; Xin-Hua Chen (Marine Life Science & Technology, 2024)

Prevalence and implications of microplastic contaminants in general human seminal fluid: A Raman spectroscopic study - Ning Li; Huijun Yang; Yunling Dong; Bin Wei; Liyang Liang; Xiang Yun; Jiaqi Tian; Yongfei Zheng; Shuyin Duan; Lin Zhang (Science of The Total Environment, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Spatiotemporal variations and risk assessment of estrogens in the water of the southern Bohai Sea: A comprehensive investigation spanning three years - Shuang Lu; Jing Wang; Baodong Wang; Ming Xin; Chunye Lin; Xiang Gu; Maoshan Lian; Yun Li (Journal of Hazardous Materials, 2024)

Clean and efficient process for the recycling of all components from waste printed circuit boards: Pre-treatment, bio-metallurgy, and deep utilization - Chun-chen Nie; Xi-guang Li; Qian-yun Sun; Qiang Gao; Xiang-nan Zhu; Xian-jun Lyu; Lin Li; Xiao-fang You (Journal of Cleaner Production, 2024)

Sustainable strategies for recovering metallic copper from waste printed circuit boards: Clean leaching and micro-nano copper powder preparation - Xi-guang Li; Shun-xiang Shi; Shuai Yan; Lin Li; Xi-zhuang Qin; Xiang-nan Zhu (Journal of Environmental Chemical Engineering, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

CA1 Modulates the Osteogenic Differentiation of Dental Follicle Stem Cells by Activating the BMP Signaling Pathway In Vitro - Jin-ze Zhao; Ying-Ying Ge; Ling-fa Xue; Yao-xiang Xu; Jin Yue; Cong Li; Wen-lin Xiao (Tissue Engineering and Regenerative Medicine, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Inhibitory effect of ammonium conversion by deep nitrogen application effectively reduces gaseous nitrogen losses - Changhong Liu; Yanjie Qu; Changjie Feng; Yongqiao Zhang; Shiyu Li; Zhenhua Lei; Haowei Feng; Xiang Lin; Dong Wang (Agriculture, Ecosystems & Environment, 2024)

Stabilized Hf-doped Ti/Sb-SnO2 electrode for efficient degradation of tetracycline - Danni Li; Xin Guo; Xiang Shao; Anhui Zhou; Lin Zhu; Yuting Zhang; Binbin Li; Yan Du; Limei Cao; Ji Yang (Environmental Science and Pollution Research, 2024)

Ambient air pollution, lifestyle, and genetic predisposition on all-cause and cause-specific mortality: A prospective cohort study - Yiqun Zhu; Yao Wu; Jun Cheng; Huaying Liang; Qinyu Chang; Fengyu Lin; Dianwu Li; Xin Zhou; Xiang Chen; Pinhua Pan; Hong Liu; Yuming Guo; et al. (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Phellintremulins A-C, antinociceptive sesquiterpenoids from the medicinal fungus Phellinus tremulae - Chun Tian; Li-Tang Sun; Tian Jin; Lin-Lin Yuan; Wei-Fang Xu; Hui-Xiang Yang; Tao Feng; Ji-Kai Liu (Phytochemistry, 2024)

Benzo[a]pyrene evokes epithelial-mesenchymal transition and pulmonary fibrosis through AhR-mediated Nrf2-p62 signaling - Meng-Die Li; Li-Hong Chen; Hui-Xian Xiang; Ya-Lin Jiang; Bian-Bian Lv; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Sustainable and efficient deep eutectic solvents in recycling of spent lithium-ion batteries: Recent advances and perspectives - Wen-hao Gao; Chun-chen Nie; Lin Li; Shuai Yan; Wen-tao Zhou; Xiang-nan Zhu (Journal of Cleaner Production, 2024)

Based on hydrogen and disulfide-mediated bonds, l-lysine and l-arginine enhanced the gel properties of low-salt mixed shrimp surimi (Antarctic krill and Pacific white shrimp) - Hao Man; Peizi Sun; Junxin Lin; Xiang Ren; Dongmei Li (Food Chemistry, 2024)

Dual regulation of the orderly aggregation of covalent organic frameworks at the molecular level and nanoscale to achieve efficient phototherapy and gene therapy - Tong Li; Dianwei Wang; Meng Meng; Xiaoya Guo; Lin Lin; Zhiyu Yang; Zhen Li; Longwei Xiang; Cong Liu; Jie Chen; Xuan Pang; Kai Hao; et al. (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Targeted Therapy of Spinal Cord Injury: Inhibition of Apoptosis Is a Promising Therapeutic Strategy - Wei He; Zhi-qiang Li; Hou-yun Gu; Qi-lin Pan; Fei-xiang Lin (Molecular Neurobiology, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Coating seeds with biopolymers extracted from waste-activated sludge - Chen Shi; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Shi-Ming Su; Zhongfang Lei; Xiao-Di Hao (Sustainable Chemistry and Pharmacy, 2024)

Integrated transcriptomics and metabolomics revealed the mechanism of catechin biosynthesis in response to lead stress in tung tree (Vernicia fordii) - Xiang Dong; Wenying Li; Changzhu Li; Otobong Donald Akan; Chancan Liao; Jie Cao; Lin Zhang (Science of The Total Environment, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Mechanism of color change in Antarctic krill oil during storage - Xiang-Bo Zeng; Fa-Wen Yin; Guan-Hua Zhao; Chao Guo; De-Yang Li; Hui-Lin Liu; Lei Qin; Fereidoon Shahidi; Da-Yong Zhou (Food Chemistry, 2024)

Effect of nitro-substituted ending group on the photovoltaic and photocatalytic performance of non-fullerene acceptors - Jing Wang; Junwei Zhu; Chenxi Li; Yi Lin; Xiang Li; Hongyan Zhang; Zaifei Ma; Yan Lu (Chemical Engineering Journal, 2024)

Electrospun nanofibers-derived functional scaffolds for cancer therapy - Gaizhen Kuang; Xiang Lin; Jinbo Li; Weijian Sun; Qingfei Zhang; Yuanjin Zhao (Chemical Engineering Journal, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

Performance on adsorption of toluene by ionic liquid-modified AC in high-humidity exhaust gas - Ji-feng Guo; Zhao-li Ping; Nan Liu; Xin Zhang; Jia-lin Lv; Yan-yan Yao; Jia-jun Hu; Wen-juan Wang; Ji-xiang Li (Environmental Science and Pollution Research, 2024)

SoybeanNet: Transformer-based convolutional neural network for soybean pod counting from Unmanned Aerial Vehicle (UAV) images - Jiajia Li; Raju Thada Magar; Dong Chen; Feng Lin; Dechun Wang; Xiang Yin; Weichao Zhuang; Zhaojian Li (Computers and Electronics in Agriculture, 2024)

Assessing daytime discrepancies and key factors in urban thermal environments: A local climate zones-based modeling study in five Chinese cities - Zhuo Liu; Hua Yuan; Wenzong Dong; Yingying Liu; Yizhou Zhang; Xianxiang Li; Jiayi Xiang; Wanyi Lin; Jiahao Shi; Yongjiu Dai (Urban Climate, 2024)

Strategic choice of the management of disposable meal boxes from the perspectives of life cycle impact assessment: Recycling fossil plastics or promoting biogenic plastics - Guannv Lin; Jiayi Yuan; Xiang Li; Silan Zhao; Shengwei Wang; Huimin Chang; Yan Zhao (Resources, Conservation and Recycling, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Spatial distribution characteristics of carbazole and polyhalogenated carbazoles in water column and sediments in the open Western Pacific Ocean - Songtao Hu; Lijia Jiang; Lingbo Jiang; Leiming Tang; Anura Upasanta Kumara Wickrama Arachchige; Hao Yu; Zhaochao Deng; Longyu Li; Chunsheng Wang; Dongsheng Zhang; Chunlei Chen; Shiquan Lin; et al. (Journal of Hazardous Materials, 2024)

Nitrogen losses trade-offs through layered fertilization to improve nitrogen nutrition status and net economic benefit in wheat-maize rotation system - Changhong Liu; Shengyan Pang; Xiufeng Li; Yongqiang Li; Jinwei Li; Ruoling Ma; Xiang Lin; Dong Wang (Field Crops Research, 2024)

Polydopamine-integrated tumor decellularized extracellular matrix hydrogel microparticles for wound healing - Gongting Zhou; Xiang Lin; Wenzhao Li; Hongzheng Li; Qingfei Zhang; Xiaoya Ding; Weijian Sun (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Diagenetic alterations induced by lamina-scale mass transfer and the impacts on shale oil reservoir formation in carbonate-rich shale of the Permian Lucaogou Formation, Jimusar Sag - Ke Li; Kelai Xi; Yingchang Cao; Xiang Shan; Miruo Lin (Marine and Petroleum Geology, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Enhanced peroxymonosulfate activation via MOF-derived bimetal core-shell Co-Fe@NC hybrids to degrade emerging pollutants - Hui Li; Xinlei Ren; Wenxue Pan; Shiting Zhu; Jin Zhang; Zhiyuan Yang; Liu Qian; Yueying Wang; Yujing Huang; Lin Guo; Minghui Xiang (Journal of Environmental Chemical Engineering, 2024)

Cobalt doping amount determines dominant reactive species in peroxymonosulfate activation via porous carbon catalysts co-doped by cobalt and nitrogen - Xiang Li; Limeng Wu; Aiqin Zhang; Shaohua Wu; Yan Lin; Chunping Yang (Journal of Environmental Sciences, 2024)

The Pacific-North American teleconnection in the Cenozoic - Zhibo Li; Yongyun Hu; Jian Zhang; Xiang Li; Jiaqi Guo; Jiawenjing Lan; Qifan Lin; Shuai Yuan; Mengyu Wei; Zihan Yin; Qiang Wei; Xiujuan Bao; et al. (Global and Planetary Change, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Regulating framework aluminum location towards boosted light olefins generation in ex-situ catalytic pyrolysis of low-density polyethylene - Ting Wang; Xiang Feng; Dong Lin; Yan Li; Jingyuan Shang; Jinqing Zhang; Shuo Li; Yibin Liu; Hui Zhao; Zhe Ma; Xiaobo Chen; Xingong Zhang; et al. (Chemical Engineering Journal, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Chemical structure of hydrocarbons significantly affects removal performance and microbial responses in gas biotrickling filters - Xin Wu; Yan Lin; Yongyi Wang; Mei Dai; Shaohua Wu; Xiang Li; Chunping Yang (Bioresource Technology, 2024)

The Characteristics of Degradation of Enrofloxacin by Vis / BC-BiOI / PMS Photocatalytic System Based on BiOI-Modified Biochar - Yutong Xiang; Bin Tan; Meng Li; Yuning Liu; Xiangyu Liu; Yuwei Ding; Bing Lin; Qian Zhang (Water, Air, & Soil Pollution, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Green building practices to integrate renewable energy in the construction sector: a review - Lin Chen; Ying Hu; Ruiyi Wang; Xiang Li; Zhonghao Chen; Jianmin Hua; Ahmed I. Osman; Mohamed Farghali; Lepeng Huang; Jingjing Li; Liang Dong; David W. Rooney; et al. (Environmental Chemistry Letters, 2024)
The building sector is significantly contributing to climate change, pollution, and energy crises, thus requiring a rapid shift to more sustainable construction practices. Here, we review the emerging practices of integrating renewable energies in the construction sector, with a focus on energy types, policies, innovations, and perspectives. The energy sources include solar, wind, geothermal, and biomass fuels. Case studies in Seattle, USA, and Manama, Bahrain, are presented. Perspectives comprise self-sufficiency, microgrids, carbon neutrality, intelligent buildings, cost reduction, energy storage, policy support, and market recognition. Incorporating wind energy into buildings can fulfill about 15% of a building's energy requirements, while solar energy integration can elevate the renewable contribution to 83%. Financial incentives, such as a 30% subsidy for the adoption of renewable technologies, augment the appeal of these innovations.

Spawning, larval morphological ontogeny and first feeding of yellow-striped cardinalfish Ostorhinchus cyanosoma (Bleeker, 1853) - Ang Lu; Xiang-Yu Li; Yi-Yang Lin; Yen-Ju Pan (Aquaculture, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Dt1 inhibits SWEET-mediated sucrose transport to regulate photoperiod-dependent seed weight in soybean - Xiaoming Li; Zhonghui Chen; Haiyang Li; Lin Yue; Cuirong Tan; Hongjie Liu; Yilong Hu; Yuhua Yang; Xiani Yao; Lingping Kong; Xiang Huang; Bin Yu; et al. (Molecular Plant, 2024)

Resistance of CANON systems with different granules/flocs sludge ratios to alternating low-temperature operation - Siyun Liu; Bolin Li; Xiang Li; Xiangyu Lin; Wanqing Zhao; Hai Su; Mingxing Yu (Journal of Water Process Engineering, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Engineered Bacillus subtilis Biofilm@Biochar living materials for in-situ sensing and bioremediation of heavy metal ions pollution - Xiaojuan Zhu; Qinyuan Xiang; Lin Chen; Jianshu Chen; Lei Wang; Ning Jiang; Xiangrui Hao; Hongyan Zhang; Xinhua Wang; Yaqian Li; Rabia Omer; Lingfan Zhang; et al. (Journal of Hazardous Materials, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Aboveground plants determine the exchange of pathogens within air-phyllosphere-soil continuum in urban greenspaces - Changyi Lu; Zufei Xiao; Hu Li; Ruixia Han; Anqi Sun; Qian Xiang; Zhe Zhu; Gang Li; Xiaoru Yang; Yong-Guan Zhu; Qing-Lin Chen (Journal of Hazardous Materials, 2024)

Nanoplastic propels diet-induced NAFL to NASH via ER-mitochondrial tether-controlled redox switch - Jie Wei; Jintao Liu; Huan Wang; Kai Wen; Xiuye Ni; Yilong Lin; Jingru Huang; Xiang You; Zhao Lei; Juan Li; Heqing Shen; Yi Lin (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Behavior of FRP-engineered cementitious composite layer and concrete interface with FRP anchors - Wei-Wen Li; Jie Liu; Qian-Xiang Lin; Xu Yang; Eskinder Desta Shumuye; Wang Peng (Engineering Structures, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Effect of different operation conditions on PCDD/F inhibition by ammonium dihydrogen phosphate: concentrations, distributions and mechanisms - Jiayao Wu; Weican Xiang; Xiaoxiao Wang; Wenlong Song; Yuxuan Ying; Xiaoqing Lin; Xiaodong Li (Waste Disposal & Sustainable Energy, 2024)

Optimization of Microwave Presplitting Iron Ore to Improve Mechanical Mining Efficiency - Feng Lin; Xia-ting Feng; Shi-ping Li; Jiu-yu Zhang; Xiang-xin Su; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)

Cathepsin B degrades RbcL during freezing-induced programmed cell death in Arabidopsis - Gang Yang; Tao Chen; Ting-ting Fan; Xiang-yu Lin; Yu-qiong Cui; Wei-chao Dong; Li-zhe An; Hua Zhang (Plant Cell Reports, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Estimation of annual soil CO2 efflux under the erosion and deposition conditions by measuring and modeling its respiration rate in southern China - Geng Guo; Xiao Li; Jie Kuai; Xiang Zhang; Xiaoying Peng; Yanyin Xu; Guangruo Zeng; Jun Liu; Chen Zhang; Jie Lin (Journal of Environmental Management, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

Sustainable paramylon production from food waste by Euglena gracilis using a waste-based cell immobilisation technique - Jin-Hua Mou; Si-Fen Liu; Li-Li Yang; Zi-Hao Qin; Yu-Feng Yang; Zhen-Yao Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2024)

Diagenetic effects on strontium isotopes in shallow-water carbonate sediments from Middle Miocene to Recent - Xinran Chen; Mengchun Cao; Thomas J. Algeo; Na Li; Guang-yi Wei; Yi-bo Lin; Hua Zhang; Lei Xiang; Youhua Zhu; Changgui Xu; Caiwei Fan; Shuzhong Shen; et al. (Chemical Geology, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Oncogenic lncRNA FAM215A promotes the malignant cell phenotypes of acute myeloid leukemia (AML) cell lines - Lin Li; Liuyan Xin; Xiang Yang; Zhengrong Zou (Journal of Molecular Histology, 2024)

Interactive effects of dietary leucine and isoleucine affect amino acid profile and metabolism through AKT/TOR signaling pathways in blunt snout bream (Megalobrama amblycephala) - Mang-mang Wang; Yang-yang Huang; Wen-bin Liu; Kang Xiao; Xi Wang; Hui-xing Guo; Yi-lin Zhang; Jing-Wei Fan; Xiang-fei Li; Guang-zhen Jiang (Fish Physiology and Biochemistry, 2024)

The changes and correlation of IL-6 and oxidative stress levels in RAW264.7 macrophage cells induced by PAHs in PM2.5 - Jiaxin Liu; Hongqiu Li; Ziwei Guo; Xiang Xiao; Angelo Viscardi; Rongqi Xiang; Haobiao Liu; Xue Lin; Jing Han (Environmental Geochemistry and Health, 2024)

Design and analysis of an electro-adhesive hexapod robot with convertible limbs in microgravity - Ao Xiang; Lin Zhang; Li Fan (Advances in Space Research, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

One new limonoid with cytotoxicity against glioma cell lines from Cipadessa baccifera - Zhao Kun; Li Lin; Zheng Xiang (Natural Product Research, 2024)

Study on fractional-order elastic-plastic constitutive model of river silt based on critical state theory - Yuke Wang; Junhao Li; Xiang Yu; Xiaoying Lin; Jinggan Shao; Jiancang Zhao (Marine Georesources & Geotechnology, 2024)

Effects of uranium mining on soil bacterial communities and functions in the Qinghai-Tibet plateau - Qiang Li; Zhuang Xiong; Peng Xiang; Lin Zhou; Ting Zhang; Qian Wu; Changsong Zhao (Chemosphere, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Polarization-dependent photoinduced metal–insulator transitions in manganites - Lina Deng; Weiye Zhang; Hanxuan Lin; Lifen Xiang; Ying Xu; Yadi Wang; Qiang Li; Yinyan Zhu; Xiaodong Zhou; Wenbin Wang; Lifeng Yin; Hangwen Guo; et al. (Science Bulletin, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Reduced contribution of microbial necromass carbon to soil organic carbon following tunnel construction in the eastern Qinghai-Tibet Plateau - Yuzhuo Chen; Jincheng Xiang; Xiaodong Wang; Yang Xiao; Benjamin Laffitte; Shurui He; Du Yu; Guo Chen; Lin Li; Xiangjun Pei; Xiaolu Tang (Journal of Cleaner Production, 2024)

Net effect of air pollution controls on health risk in the Beijing–Tianjin–Hebei region during the 2022 winter Olympics and Paralympics - Changqing Lin; Peter K.K. Louie; Alexis K.H. Lau; Jimmy C.H. Fung; Zibing Yuan; Minghui Tao; Xuguo Zhang; Md. Shakhaoat Hossain; Chengcai Li; Xiang Qian Lao (Journal of Environmental Sciences, 2024)

Activation of peroxymonosulfate by sewage sludge-derived biochar to promote short-chain fatty acid production during sludge anaerobic fermentation - Jinling He; Qingchen Wu; Nan Jiang; Ai Zhang; Lin Wang; Xiang Li; Gang Xue; Hong Chen; Pin Gao (Chemical Engineering Journal, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Ammonium intercalation engineering regulated structural stability of V6O13 cathodes for durable zinc ion batteries - Ziang Wu; Jia Yao; Chi Chen; Xiang Chen; Xiaoxin Pan; Junjie Zheng; Yi Gan; Jingying Li; Xingtai Liu; Chao Xia; Lin Lv; Hao Wang; et al. (Chemical Engineering Journal, 2024)

High-yield and scalable cellulose nanomesh preparation via dilute acid vapor and enzymatic hydrolysis-mediated nanofabrication - Xiaowen Li; Zhongrun Xiang; Wanting Dang; Zewan Lin; Huai Wang; Huiqing Wang; Dongdong Ye; Risheng Yao (Carbohydrate Polymers, 2024)

Investigation and optimization of outdoor thermal comfort in elementary school campuses: Example from a humid-hot area in China - Tongye Guo; Zhaoxia Lin; Yang Zhao; Zhaosong Fang; Yini Fan; Xiang Zhang; Jiahao Yang; Yuankui Li (Building and Environment, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Spatio-temporal variation of toxin-producing gene abundance in Microcystis aeruginosa from Poyang Lake - Lin Wu; Li Zhang; Lijuan Yuan; Qiegen Liao; Jianjun Xiang; Dawen Zhang; Tong Qiu; Jutao Liu; Junhui Guo (Environmental Science and Pollution Research, 2023)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

The variability in CYP3A4 activity determines the metabolic kinetic characteristics of ketamine - Mengfang Li; Qingqing Li; Dan Lin; Xiang Zheng; Lehao Jin; Jianping Cai; Guoxin Hu; Jianchang Qian (Toxicology, 2023)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Hydraulic circulation technology remediates the contaminated groundwater with petroleum hydrocarbon: Evidence from laboratory and field tests - Zhan Chen; Yu-Lin Wu; Tao Li; Yi-Xiang Wang; Ling-Kang Xuan; Shi-Feng Lu (Journal of Cleaner Production, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Impact of L-arginine on the quality of heat-treated Antarctic krill: Influence of pH and the guanidinium group - Xiang Ren; Xinyu Zhang; Peizi Sun; Junxin Lin; Yuying Zhang; Dongmei Li (Food Research International, 2023)

In vivo-in vitro correlations (IVIVC) for the assessment of pyrethroid bioavailability in honey - Yuying Liu; Siyuan Jiang; Yuxin Xiang; Fengxiang Lin; Xingyu Yue; Minkun Li; Jinjing Xiao; Haiqun Cao; Yanhong Shi (Food Chemistry, 2023)

Multiomics reveals the formation pathway of volatile compounds in preserved egg yolk (PEY) induced by NaCl: Based on the model of PEY and salted egg yolk (SEY) treated with/without NaCl - Xiaole Xiang; Le Chen; Shiqin Dong; Faxiang Wang; Xianghong Li; Yiqun Huang; Yongle Liu; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2023)

Artemisia selengensis Turcz. leaves extract ameliorates hyperuricemia in mice by inhibiting hepatic xanthine oxidase activity, modulating renal uric acid transporters, and improving metabolic disorders - Lin Xiang; Yuting Huang; Rong Li; Yexing Tao; Ting Wu; Siyi Pan; Xiaoyun Xu (Food Bioscience, 2023)

Human milk oligosaccharides in milk of mothers with term and preterm delivery at different lactation stage - Chuncui Huang; Yue Lu; Lin Kong; Zhendong Guo; Keli Zhao; Zheng Xiang; Xinyue Ma; Huanyu Gao; Yongfang Liu; Zhongmin Gao; Lijuan Xu; Wengang Chai; et al. (Carbohydrate Polymers, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Denitrification effect and strengthening mechanism of SAD/A system at low temperature by gel-immobilization technology - Xiangyu Lin; Bolin Li; Mengyuan Tian; Xiang Li; Jun Wang (Science of The Total Environment, 2023)

Circumstellar material ejected violently by a massive star immediately before its death - Jujia Zhang; Han Lin; Xiaofeng Wang; Zeyi Zhao; Liping Li; Jialian Liu; Shengyu Yan; Danfeng Xiang; Huijuan Wang; Jinming Bai (Science Bulletin, 2023)

Interaction of derivatives of cellulose and lignin in co-HTC, co-pyrolysis and co-activation - Jingyi Liang; Haisheng Lin; Chao Li; Lijun Zhang; Shu Zhang; Shuang Wang; Jun Xiang; Song Hu; Yi Wang; Xun Hu (Fuel, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Stretchable textile with ultra-high electromagnetic interference shielding performance based on porous wrinkled conductive network - Tai-Bao Yang; Ji-You Zong; Hao Lin; Ding-Xiang Yan; Jun Lei; Zhong-Ming Li (Chemical Engineering Journal, 2023)

Synergistic effects and mechanisms of plasma coupled with peracetic acid in enhancing short-chain fatty acid production from sludge: Motivation of reactive species and metabolic tuning of microbial communities - Nan Jiang; Ai Zhang; Andere Clement Miruka; Lin Wang; Xiang Li; Gang Xue; Yanan Liu (Bioresource Technology, 2023)

Utilization of lipidic food waste as low-cost nutrients for enhancing the potentiality of biofuel production from engineered diatom under temperature variations - Yu-Feng Yang; Guang-Bin Ye; Hua-Jun Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiao-Fei Zheng; Arivalagan Pugazhendhi; Xiang Wang (Bioresource Technology, 2023)

Bacterial metabolism-triggered-chemiluminescence-based point-of-care testing platform for sensitive detection and photothermal inactivation of Staphylococcus aureus - Xinghui Yu; Yongqiang Ma; Siyuan Liu; Chunchun Qi; Weiqi Zhang; Wen Xiang; Zhaoxian Li; Kai Yang; Shaoxian Duan; Xinrao Du; Jian Yu; Yan Xie; et al. (Analytica Chimica Acta, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Generation and engineering applications of sulfate radicals in environmental remediation - Jun Xie; Chunping Yang; Xiang Li; Shaohua Wu; Yan Lin (Chemosphere, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Stress of cupric ion and oxytetracycline in Chlorella vulgaris cultured in swine wastewater - Yun Luo; Xiang Li; Yan Lin; Shaohua Wu; Jay J. Cheng; Chunping Yang (Science of The Total Environment, 2023)

Culturable and inhalable airborne bacteria in a semiunderground municipal wastewater treatment plant: Distribution, transmission, and health risk assessment - Xiang Zhang; Bingjie Lu; Guang Chen; Lihua Wang; Bingjie Lin; Zhengliang Peng; Songliu Lu; Dan Li; Jianmin Chen (Journal of Hazardous Materials, 2023)

Catalytic activity and reaction mechanisms of single-atom metals anchored on nitrogen-doped carbons for peroxymonosulfate activation - Shaohua Wu; Zhongwen Yang; Ziyang Zhou; Xiang Li; Yan Lin; Jay J. Cheng; Chunping Yang (Journal of Hazardous Materials, 2023)

Impact of bentonite on greenhouse gas emissions during pig manure composting and its subsequent application - Jia-Ping Wu; Meng-Ling Li; Yan Wang; Shan Lin; Rong-Gui Hu; Rong-Biao Xiang (Journal of Environmental Management, 2023)

Surface fabrication of silica aerogels from inorganic precursor achieving elastic and superhydrophobic sponges for oil-water separation - Xiang Li; Xiaoxiao Huang; Qingge Feng; Zheng Liu; Dongbo Wang; Dachao Ma; Lin Feng; Chen Zuo; Junyi Liu; Sinan Wang; Zhuoyan Huang; Xiaodie Cheng; et al. (Journal of Environmental Chemical Engineering, 2023)

Supplemental irrigation at the jointing stage of late sown winter wheat for increased production and water use efficiency - Sen Wang; Yuxi Niu; Li Shang; Zhenyan Li; Xiang Lin; Dong Wang (Field Crops Research, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

Effect of composition of volatile fatty acids on yield of polyhydroxyalkanoates and mechanisms of bioconversion from activated sludge - Ziying Zhang; Yan Lin; Shaohua Wu; Xiang Li; Jay J. Cheng; Chunping Yang (Bioresource Technology, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

DJ-1-mediated p62 degradation delays intervertebral disc degeneration by inhibiting apoptosis of nucleus pulposus cells - Jialiang Lin; Xuanqi Zheng; Zhencheng Xiong; Qian Xiang; Yongzhao Zhao; Shuai Jiang; Zhuoran Sun; Dongwei Fan; Chuiguo Sun; Weishi Li (Apoptosis, 2023)

Prussian blue analogues derived magnetic FeCo@GC material as high-performance metallic peroxymonosulfate activators to degrade tetrabromobisphenol A over a wide pH range - Liu Qian; Hui Li; Dengsong Zhang; Lin Guo; Wenxue Pan; Jin Zhang; Minghui Xiang (Environmental Science and Pollution Research, 2023)

Fabrication of durable self-cleaning photocatalytic coating with long-term effective natural light photocatalytic degradation performance - Jinghang Feng; Qingge Feng; Jingbo Xin; Qihua Liang; Xiang Li; Kao Chen; Jiayang Teng; Sinan Wang; Lin Feng; Junyi Liu (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Skeleton engineering of rigid covalent organic frameworks to alter the number of binding sites for improved radionuclide extraction - Xiangbin Lin; Weiwen Xin; Shusen Chen; Yan Song; Linsen Yang; Yongchao Qian; Lin Fu; Yanglansen Cui; Xiaofeng He; Tinyang Li; Zhehua Zhang; Yadong Wu; et al. (Journal of Hazardous Materials, 2023)

Revealing the mechanism underlying the effects of γ-aminobutyric acid-dioscorin interactions on dioscorin structure and emulsifying properties by molecular dynamic simulations - Yun-long Chen; Hao-nan Nie; Hui Dong; Qi Gao; Xue Peng; Ning Wang; Xueling Chen; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Research International, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Characteristics of digested sludge-derived biochar for promoting methane production during anaerobic digestion of waste activated sludge - Shengye Duan; Junguo He; Xiaodong Xin; Lin Li; Xiang Zou; Yijie Zhong; Jie Zhang; Xinxin Cui (Bioresource Technology, 2023)

Transcriptome analysis reveals important regulatory genes and pathways for tuber color variation in Pinellia ternata (Thunb.) Breit - Cong Yin; Ding Tang; Xiaoyu Liu; Zihan Li; Yulin Xiang; Kaiming Gao; Heyu Li; Lin Yuan; Bisheng Huang; Juan Li (Protoplasma, 2023)

Large yellow croaker (Larimichthys crocea) mitofusin 2 inhibits type I IFN responses by degrading MAVS via enhanced K48-linked ubiquitination - Wen-Xing Li; Xiao-Hong Wang; Yi-Jun Lin; Yuan-Yuan Zhou; Jun Li; Xiang-Yang Zhang; Xin-Hua Chen (Marine Life Science & Technology, 2023)
In mammals, mitofusin 2 (MFN2) is involved in mitochondrial fusion, and suppresses the virus-induced RIG-I-like receptor (RLR) signaling pathway. However, little is known about the function of MFN2 in non-mammalian species. In the present study, we cloned an MFN2 ortholog ( Lc MFN2) in large yellow croaker ( Larimichthys crocea ). Phylogenetic analysis showed that MFN2 emerged after the divergence of amphioxus and vertebrates. The protein sequences of MFN2 were well conserved from fish to mammals. Lc MFN2 was expressed in all the tissues/organs examined at different levels, and its expression was upregulated in response to poly(I:C) stimulation. Overexpression of Lc MFN2 inhibited MAVS-induced type I interferon (IFN) promoter activation and antiviral gene expression. In contrast, knockdown of endogenous Lc MFN2 enhanced poly(I:C) induced production of type I IFNs. Additionally, Lc MFN2 enhanced K48-linked polyubiquitination of MAVS, promoting its degradation. Also, overexpression of Lc MFN2 impaired the cellular antiviral response, as evidenced by the increased expression of viral genes and more severe cytopathic effects (CPE) in cells infected with spring viremia of carp virus (SVCV). These results indicated that Lc MFN2 inhibited type I IFN response by degrading MAVS, suggesting its negative regulatory role in cellular antiviral response. Therefore, our study sheds a new light on the regulatory mechanisms of the cellular antiviral response in teleosts.

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Water-dispersible and stable polydopamine coated cellulose nanocrystal-MXene composites for high transparent, adhesive and conductive hydrogels - Bolin Wan; Nana Liu; Zhen Zhang; Xiong Fang; Yugao Ding; Haosheng Xiang; Yunqing He; Mingxian Liu; Xiaoming Lin; Juntao Tang; Yingzhan Li; Biao Tang; et al. (Carbohydrate Polymers, 2023)

Combined effects of oxytetracycline concentration and organic loading rate on semi-continuous anaerobic digestion of swine wastewater - Zhiwei Huang; Qiuya Niu; Wenkai Nie; Yan Lin; Shaohua Wu; Xiang Li; Jay J. Cheng; Chunping Yang (Bioresource Technology, 2023)

Dust storm forecasting through coupling LOTOS-EUROS with localized ensemble Kalman filter - Mijie Pang; Jianbing Jin; Arjo Segers; Huiya Jiang; Li Fang; Hai Xiang Lin; Hong Liao (Atmospheric Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Seismic performance and damage properties of flexure–shear critical RC columns with various loading cycles - Qin Zhang; Ming-Hui Chen; Wen-Jie Li; Xiang-Lin Gu; Jin-Xin Gong (Bulletin of Earthquake Engineering, 2023)

Positive responses and mechanisms of nitrifying sludge to carbon quantum dots: reactor performance, microbial behavior, and antioxidant defense - Lin-Kai Guo; Lei Yang; Shen Cui; Zhao Sun; Xiao-Tong Li; Yu-Chao Wang; Yu-Cai Li; Yong-Xiang Ren (Environmental Science and Pollution Research, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Horseradish peroxidase (HRP) and glucose oxidase (GOX) based dual-enzyme system: Sustainable release of H2O2 and its effect on the desirable ping pong bibi degradation mechanism - Xiangyu Liu; Qian Zhang; Meng Li; Song Qin; Ziqi Zhao; Bing Lin; Yuwei Ding; Yutong Xiang; Chengwei Li (Environmental Research, 2023)

Gut microbiota and ionizing radiation-induced damage: Is there a link? - Yueqiu Yu; Xiang Lin; Feiyang Feng; Yuanyun Wei; Shuang Wei; Yaqi Gong; Caimao Guo; Qingyu Wang; Peimeng Shuai; Tiantian Wang; Hui Qin; Guoqing Li; et al. (Environmental Research, 2023)

A series of bifunctional ReBaCo2O5+ perovskite catalysts towards intermediate-temperature oxygen reduction reaction and oxygen evolution reaction - Lin Li; Ziwei Dong; Tian Xia; Xiang Li; Qiang Li; Liping Sun; Hui Zhao; Lihua Huo (Chemical Engineering Journal, 2023)

Navigating practical applications of food waste valorisation based on the effects of food waste origins and storage conditions - Jin-Hua Mou; Zi-Hao Qin; Yu-Feng Yang; Si-Fen Liu; Wei Yan; Lan Zheng; Ya-Hui Miao; Hong-Ye Li; Patrick Fickers; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Differences in the diversity and community structure of the intestinal microbiota of commercial fishes in the central and southern East China Sea in spring and autumn - Jiali Xiang; Shigang Liu; Puqing Song; Ran Zhang; Yuan Li; Longshan Lin (Environmental Biology of Fishes, 2023)

Geographical variation in community‐wide herbivory matches patterns of intraspecific variation instead of species turnover - Xiang Liu; Ziyuan Lin; Kui Hu; Xingxing Wang; Peng Zhang; Yao Xiao; Li Zhang; Mu Liu (Global Ecology and Biogeography, 2023)
Aim Attempts over the past 30 years to explain geographical variation in the strength of herbivore pressure have given rise to ecological hypotheses like the latitudinal herbivory hypothesis. This hypothesis, however, has rarely been tested using community‐level data. Therefore, the aim of our study was to examine the patterns and potential mechanisms underlying geographical variation in community‐wide herbivory. Location The Qinghai‐Tibetan Plateau. Time Period July 2021. Major Taxa Studied Plants. Methods We selected 43 grassland sites along a 1500‐km latitudinal gradient ( c . 27°N to 39°N) and a 2698‐m elevational gradient (1886–4584 m) on the Qinghai‐Tibetan Plateau. We evaluated geographical patterns in invertebrate herbivory pressure at the population and community levels, while also evaluating the importance of geographical variation in mediating the effects of abiotic and biotic factors on intraspecific variation (through changes in herbivory on component species) and species turnover effects (through changes in plant community composition). Results Community‐wide herbivory decreased with latitude, mirroring intraspecific variation, while species turnover effects did not vary along any tested geographical gradients. Furthermore, we found that geographical variation in community‐wide herbivory was strongly positively correlated with soil nitrogen content. We also found a positive effect of soil nitrogen content on intraspecific variation and a negative effect of plant community biomass on species turnover effects. Main Conclusions The latitudinal gradient in community‐wide herbivory was primarily mediated by intraspecific variation, which was in turn associated with a gradient in soil nitrogen content. Our findings highlight the need for community‐wide assessments of geographical variation in plant–herbivore interactions, decomposing community‐wide herbivory into intraspecific variation and species turnover effects.

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

Effect of salinity stress on nitrogen and sulfur removal performance of short-cut sulfur autotrophic denitrification and anammox coupling system - Xiang Li; Yan Yuan; Pengze Dang; Bo-lin Li; Yong Huang; Wei Li; Mao Zhang; Miao Shi; Ziqi Shen; Linyan Xie (Science of The Total Environment, 2023)

Development of an efficient insecticide substrate and inhibitor screening system of insect P450s using fission yeast - Xiang Li; Lianyun Lin; Zhi Li; Hadiatullah Hadiatullah; Shishir Sharma; He Du; Xin Yang; Wei Chen; Shijun You; Matthias Bureik; Zhiguang Yuchi (Insect Biochemistry and Molecular Biology, 2023)

Phenylpropanoids from the Nitraria tangutorum fruit as glycerol phosphate dehydrogenase inhibitors through in vitro, in silico and in vivo studies - Zhi-Xiang Liu; Lin-Lin Yuan; Nan Zhang; Min Zhao; Yue Li; Ming-Yue Zhao; Yu-Meng Wang; Zi-Zhuo Wang; Yang-Yang Zhang; Jin-Long Tian (Food Bioscience, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Molecular cloning and functional analysis of polymeric immunoglobulin receptor, pIgR, gene in mandarin fish Siniperca chuatsi - Jia Xiang Ji; Lin Zhang; Li Li; Kai Lun Wang; Jing Hou; Lan Hao Liu; Bo Li; Bai Dong Zhang; Nan Li; Shan Nan Chen; Pin Nie (Fish & Shellfish Immunology, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Cytochrome P450-mediated co-metabolism of fluoroquinolones by Haematococcus lacustris for simultaneously promoting astaxanthin and lipid accumulation - Xiang Wang; Zhong-Hong Zhang; Kuan-Kuan Yuan; Hui-Ying Xu; Guo-Hui He; Libin Yang; Joseph Buhagiar; Wei-Dong Yang; Yalei Zhang; Carol Sze Ki Lin; Hong-Ye Li (Chemical Engineering Journal, 2023)

Chitosan-Fe3O4 composites enhance anaerobic digestion of liquor wastewater under acidic stress - Wenkai Nie; Yan Lin; Xin Wu; Shaohua Wu; Xiang Li; Jay J. Cheng; Chunping Yang (Bioresource Technology, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Metabolomics reveals size-dependent persistence and reversibility of silver nanoparticles toxicity in freshwater algae - Lin Shen; Qin Qin Li; Yu Hang Kang; Qian Qian Xiang; Xia Luo; Li Qiang Chen (Aquatic Toxicology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

The journey of prochloraz pesticide in Citrus sinensis: Residual distribution, impact on transcriptomic profiling and reduction by plasma-activated water - Qianwei Lin; Yuanwei Huang; Gangfeng Li; Zisheng Luo; Lei Wang; Dong Li; Yizhou Xiang; Lingling Liu; Zhaojun Ban; Li Li (Journal of Hazardous Materials, 2023)

Environmental profiling microalgae-based eicosapentaenoic acid production along the technical advancement via life cycle assessment - Zi-Hao Qin; Xiaomeng Hu; Jin-Hua Mou; Guo-Hui He; Guang-Bin Ye; Hong-Ye Li; Shauhrat Singh Chopra; Liang Dong; Carol Sze Ki Lin; Xiang Wang (Journal of Cleaner Production, 2023)

Water transport in continental subduction zones: Constraints from eclogite from the Dabie orogen, east-central China - Zhi-Min Wang; Ren-Xu Chen; Yong-Fei Zheng; Shuning Li; Lin Zhu; Bing Gong; Xiang-Ping Zha; Wan-Cai Li (Journal of Asian Earth Sciences, 2023)

Integrative analyses of transcriptome and metabolome reveal comprehensive mechanisms of Epigallocatechin-3-gallate (EGCG) biosynthesis in response to ecological factors in tea plant (Camellia sinensis) - Ping Xiang; Qiufang Zhu; Luhuan zhang; Puzhen Xu; Lijia Liu; Yuanyuan Li; Bosi Cheng; Xingjian Wang; Jianghong Liu; Yutao Shi; Liangyu Wu; Jinke Lin (Food Research International, 2023)

Adsorption of heavy metals on biodegradable and conventional microplastics in the Pearl River Estuary, China - Min Shi; Qun Xie; Zhen-Liang Li; Yun-Feng Pan; Zhen Yuan; Lang Lin; Xiang-Rong Xu; Heng-Xiang Li (Environmental Pollution, 2023)

Assessment of exhaled pathogenic droplet dispersion and indoor-outdoor exposure risk in urban street with naturally-ventilated buildings - Jian Hang; Xia Yang; Cui-Yun Ou; Zhi-Wen Luo; Xiao-Dan Fan; Xue-Lin Zhang; Zhong-Li Gu; Xian-Xiang Li (Building and Environment, 2023)

Preliminary identification of soil fungi for the degradation of polyurethane film - Kong-Yang Wu; Tong-Xiang Yang; Meng Yang; Jin-Qiu Wu; Xue Li; Xue-Dong Chen; Lin Tang; Xue-Yi Yang (Archives of Microbiology, 2023)

Identification and characterization of biocontrol agent Lysinibacillus boronitolerans P42 against Cerrena unicolor that causes root rot of arecanut palm - Xiang Ma; Yuxiao Gao; Hong Li; Dan Wang; Juanjuan Li; Xinwen Hu; Xi Huang; Min Lin; Yanqiong Tang; Zhu Liu (Archives of Microbiology, 2023)

circTAB2 inhibits lung cancer proliferation, migration and invasion by sponging miR-3142 to upregulate GLIS2 - Weiling Man; Yumeng Cui; Jie Li; Yanghua Li; Jie Jin; Yang Jin; Xiaojie Wu; Rongbin Zhong; Xiang Li; He Yao; Yanli Lin; Lihe Jiang; et al. (Apoptosis, 2023)

Cupric ions inducing dynamic hormesis in duckweed systems for swine wastewater treatment: Quantification, modelling and mechanisms - Chengxi Li; Yan Lin; Xiang Li; Jay J. Cheng; Chunping Yang (Science of The Total Environment, 2023)

Pore connectivity influences mass transport in natural rocks: Pore structure, gas diffusion and batch sorption studies - Xiaoqing Yuan; Qinhong Hu; Xiang Lin; Chen Zhao; Qiming Wang; Yukio Tachi; Yuta Fukatsu; Shoichiro Hamamoto; Marja Siitari-Kauppi; Xiaodong Li (Journal of Hydrology, 2023)

Potential of kerosene-diesel blends as alternative fuels for diesel engines: Perspectives from spray combustion characteristics - Zhaowen Wang; Xiaojie Li; Lin Xiang; Yuhan Huang; Bing Lang; Xiaobei Cheng; Jie Zhang (Fuel, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Influence of plants on anammox process in constructed Wetland: Irrelevance, inhibition or enhancement - Jie Li; Lin Liu; Yu-Ming Zheng; Lin Ma; Quan-Bao Zhao; Xuan Wang; Chao-Xiang Liu (Chemical Engineering Journal, 2023)

Application of improved support vector machine in geochemical lithology identification - Shitao Yin; Xiaochun Lin; Yongjian Huang; Zhifeng Zhang; Xiang Li (Earth Science Informatics, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Ambient nitrogen dioxide and cardiovascular diseases in rural regions: a time-series analyses using data from the new rural cooperative medical scheme in Fuyang, East China - Teng-Fei Dong; Zhen-Qiu Zha; Liang Sun; Ling-Li Liu; Xing-Yang Li; Yuan Wang; Xiang-Long Meng; Huai-Biao Li; Hong-Li Wang; Huan-Huan Nie; Lin-Sheng Yang (Environmental Science and Pollution Research, 2023)

Nicosulfuron stress on the glyoxalase system and endogenous hormone content in sweet maize seedlings - Zhen-Xing Wu; Jian Wang; Xiao-Hu Lin; Qing Yang; Ting-Zhen Wang; Jian-Jian Chen; Xiang-Nan Li; Yuan Guan; Gui-Hua Lv (Environmental Science and Pollution Research, 2023)

Comprehensive profiling of the distribution, risks and priority of pharmaceuticals and personal care products: A large-scale study from rivers to coastal seas - Shuang Lu; Jing Wang; Baodong Wang; Ming Xin; Chunye Lin; Xiang Gu; Maoshan Lian; Yun Li (Water Research, 2023)

Suppression on PCDD/Fs formation by a novel inhibition system consisting of phosphorous-based compounds coupled with a chlorine-deactivation material - Tong Chen; Weican Xiang; Angjian Wu; Xiaoqing Lin; Zhiliang Chen; Xiaodong Li; Jianhua Yan (Waste Management, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Genetic diversity monitoring of Chiloscyllium plagiosum from coastal Xiamen between generations - Liyan Zhang; Shigang Liu; Zizi Cai; Jiali Xiang; Puqing Song; Yueping Zhang; Yuan Li; Longshan Lin (Regional Studies in Marine Science, 2023)

Sonocatalytic removal of tetracycline in the presence of S-scheme Cu2O/BiFeO3 heterojunction: Operating parameters, mechanisms, degradation pathways and toxicological evaluation - Xin Wang; Xue-Song He; Chun-Yu Li; Shi-Lin Liu; Wen Lu; Zheng Xiang; Yang Wang (Journal of Water Process Engineering, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Tumor-targeting gene-photothermal synergistic therapies based on multifunctional polydopamine nanoparticles - Ying Zhang; Shiqi Tang; Xiaoyun Feng; Xiang Li; Jingyu Yang; Qiqi Liu; Meirong Li; Yujuan Chai; Chengbin Yang; Suxia Lin; Jia Liu (Chemical Engineering Journal, 2023)

Temporal dynamics of soil bacterial network regulate soil resistomes - Qian Xiang; Dong Zhu; Min Qiao; Xiao‐Ru Yang; Gang Li; Qing‐Lin Chen; Yong‐Guan Zhu (Environmental Microbiology, 2023)
Soil bacteria are diverse and form complicated ecological networks through various microbial interactions, which play important roles in soil multi‐functionality. However, the seasonal effects on the bacterial network, especially the relationship between bacterial network topological features and soil resistomes remains underexplored, which impedes our ability to unveil the mechanisms of the temporal‐dynamics of antibiotic resistance genes (ARGs). Here, a field investigation was conducted across four seasons at the watershed scale. We observed significant seasonal variation in bacterial networks, with lower complexity and stability in autumn, and a wider bacterial community niche in summer. Similar to bacterial communities, the co‐occurrence networks among ARGs also shift with seasonal change, particularly with respect to the topological features of the node degree, which on average was higher in summer than in the other seasons. Furthermore, the nodes with higher betweenness, stress, degree, and closeness centrality in the bacterial network showed strong relationships with the 10 major classes of ARGs. These findings highlighted the changes in the topological properties of bacterial networks that could further alter antibiotic resistance in soil. Together, our results reveal the temporal dynamics of bacterial ecological networks at the watershed scale, and provide new insights into antibiotic resistance management under environmental changes.

Associations between long-term exposure to ambient fine particulate pollution with the decline of kidney function and hyperuricemia: a longitudinal cohort study - Li-Kun Hu; Yu-Hong Liu; Kun Yang; Ning Chen; Lin-Lin Ma; Yu-Xiang Yan (Environmental Science and Pollution Research, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Layered application of phosphate fertilizer increased winter wheat yield by promoting root proliferation and phosphorus accumulation - Changhong Liu; Henghui Yan; Weiyan Wang; Ruifeng Han; Zhenyan Li; Xiang Lin; Dong Wang (Soil and Tillage Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Assessment of factors affecting the diurnal variations of atmospheric PAHs based on a numerical simulation - Zhongxiu Zhen; Yan Yin; Haowen Zhang; Jingyi Li; Jianlin Hu; Lin Li; Xiang Kuang; Kui Chen; Honglei Wang; Qingyuan Yu; Xin Zhang (Science of The Total Environment, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Tentative exploration on water-promoted catalytic ozonation of Cl-VOCs and feasibility of application in complex flue gas over monolithic cobalt catalyst - Li Xiang; Luyang Zhang; Jiaming Shao; Fawei Lin; Zhihua Wang; Beibei Yan; Guanyi Chen (Journal of Hazardous Materials, 2023)

Rational design of ordered porous nanoparticles for selective extraction of nitrobenzene compounds - Sheng Peng; Minhui Shen; Xiang Li; Yuan-Jun Tong; Jing Guo; Wei Lin; Yu-Xin Ye; Jianqiao Xu; Ningbo Zhou; Fang Zhu; Gangfeng Ouyang (Journal of Hazardous Materials, 2023)

A combined study on Vallisneria spiralis and lanthanum modified bentonite to immobilize arsenic in sediments - Wenming Yan; Xiangyu He; Tingfeng Wu; Musong Chen; Juan Lin; Xiang Chen; Qi Li; Minjuan Li; Yulin Yan; Qi Yao (Environmental Research, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

Calcination temperature regulates non-radical pathways of peroxymonosulfate activation via carbon catalysts doped by iron and nitrogen - Yue Wang; Yan Lin; Chunping Yang; Shaohua Wu; Xintao Fu; Xiang Li (Chemical Engineering Journal, 2023)

Enhancing anaerobic fermentation of waste activated sludge by investigating multiple electrochemical pretreatment conditions: Performance, modeling and microbial dynamics - Shihao Xi; Xinlei Dong; Qingshan Lin; Xiang Li; Jie Ma; Feixiang Zan; Basanta Kumar Biswal; Mukesh Kumar Awasthi; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2023)

Dual-response and lysosome-targeted fluorescent probe for viscosity and sulfur dioxide derivatives - Feng Li; Bang-Zhao Zhou; Wen Yao; Shou-Kang Sun; Jun-Ying Miao; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Progresses and challenges in sulfur autotrophic denitrification-enhanced Anammox for low carbon and efficient nitrogen removal - Xiang Li; Miao Shi; Mao Zhang; Wei Li; Pei-lin Xu; Yayi Wang; Yan Yuan; Yong Huang (Critical Reviews in Environmental Science and Technology, 2022)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

Role of carnitine in adaptation of Chromohalobacter salexigens DSM 3043 and its mutants to osmotic and temperature stress in defined medium - Xiang-Lin Meng; Xia Gao; Yuan-Ming Si; Li-Li Xu; Li-Zhong Guo; Wei-Dong Lu (Extremophiles, 2022)

The nutrient removal and tolerance mechanism of a heterotrophic nitrifying bacterium Pseudomonas putida strain NP5 under metal oxide nanoparticles stress - Huan-Huan Liu; Lei Yang; Lin-Kai Guo; Li-Xin Tu; Xiao-Tong Li; Jia Wang; Yong-Xiang Ren (Environmental Science and Pollution Research, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

The Influence of the Rotary Speed of a Microwave Applicator on Hard-Rock Fracturing Effect - Xia-ting Feng; Shi-ping Li; Cheng-xiang Yang; Feng Lin; Tian-yang Tong; Xiang-xin Su; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Exploring the Risk Thresholds of Soil Heavy Metals in Carbonate and Non-carbonate Rock Areas: The Case of Qianjiang District in Chongqing, China - Xiang Wang; Xuezhen Li; Xiaozhen Zhou; Weikang Sheng; Kun Lin; Xudong Ma (Bulletin of Environmental Contamination and Toxicology, 2022)

Two new physalins from Physalis alkekengi L. var. franchetii (Mast.) Makino - Jia-Min Sun; Ji-Xiang He; Min Huang; Hui-Xin Hu; Lin-Tao Xu; Kai-Li Fang; Xiao-Ning Wang; Tao Shen (Natural Product Research, 2022)

Brain structural connectivity sub typing in unilateral temporal lobe epilepsy - Zhensheng Li; Che Jiang; Wei Xiang; Zijuan Qi; Quwen Gao; Kairun Peng; Jian Lin; Wei Wang; Weimin Wang; Bingmei Deng (Brain Imaging and Behavior, 2022)

Effect of Zn2+-Cu2+ combined heavy metal on mechanical properties and microstructure of clayey soil - Qiang Ma; Nian-ze Wu; Heng-lin Xiao; Wen-tao Li; Jun-chen Xiang (Journal of Mountain Science, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Microplastic prevalence in marine fish from onshore Beibu Gulf, South China Sea - Jayamini Bimali Koongolla; Lang Lin; Chang-Ping Yang; Yun-Feng Pan; Heng-Xiang Li; Shan Liu; Xiang-Rong Xu (Frontiers in Marine Science, 2022)
In recent years, microplastics have been widely detected in marine fish and may pose potential risks to fish and human health. Even though microplastic pollution is a critical issue, it represents as yet non-quantified threat for some context in the marine environment. In this study, 271 individuals comprising 32 species of marine fish collected from Beibu Gulf were examined for microplastic prevalence, with an aim to provide data on the abundance, physical classification, and chemical characterization of microplastics in the great bay along South China Sea. The results showed that the occurrence rate of microplastics was 93.7%, and the average abundance of microplastics was 1.02 ± 0.18 items per individual (ranging from 0.03 to 4.00 items per individual). Microplastic accumulation was observed with a great variation in different species, body sizes, living habitats, and feeding habits of marine fishes. The dominant polymers identified by μ-FTIR were polyethylene terephthalate and polypropylene. Fibers, smaller sizes (<1 mm), and transparent color were the major characteristics of the detected microplastics, which might be important factors affecting the bioaccumulation. The present study revealed that microplastics in marine fish is a widespread issue in onshore Beibu Gulf.

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

Differentiation and Temperature Adaptation of Pampus Echinogaster Based on Genome-Wide SNPs - Yuan Li; Fangrui Lou; Shigang Liu; Hai Li; Jiali Xiang; Binbin Shan; Longshan Lin; Xuan Zhuang (Frontiers in Marine Science, 2022)
Climate change and overfishing have led to the degradation of the quality and stock of Pampus echinogaster. Exploring the genetic structure and local adaptive evolutionary mechanisms of P. echinogaster is crucial for the management of this species. This population genomic study of nine geographical populations of P. echinogaster in China was conducted by specific-locus amplified fragment sequencing (SLAF-seq). A total of 935,215 SLAF tags were obtained, and the average sequencing depth of the SLAF tags was 20.80×. After filtering, a total of 46,187 high-consistency genome-wide single nucleotide polymorphisms (SNPs) were detected. Based on all SNPs, the population size of the nine P. echinogaster geographical populations was large. The Shantou population had the lowest genetic diversity, and the Tianjin population had the highest. Moreover, the population genetic structure based on all SNPs revealed significant gene exchange and no significant genetic differentiation among the nine P. echinogaster geographical populations, probably because of the population expansion after the last glacial period, the lack of balance between migration and genetic drift, and the long-distance diffusion of eggs and larvae. We suspect that variation of material metabolism, ion transfer, breeding, stress response, and inflammatory reactions-related genes were critical for adaptation to spatially heterogeneous temperature selection in natural P. echinogaster populations.

Efficient de novo assembly and modification of large DNA fragments - Shuangying Jiang; Yuanwei Tang; Liang Xiang; Xinlu Zhu; Zelin Cai; Ling Li; Yingxi Chen; Peishuang Chen; Yuge Feng; Xin Lin; Guoqiang Li; Jafar Sharif; et al. (Science China Life Sciences, 2022)

Plane-Wave Destruction-Based Workflow for Prestack Diffraction Separation in the Shot Domain - Peng Lin; Suping Peng; Xingguo Huang; Yang Xiang; Chuangjian Li; Xiaoqin Cui (Pure and Applied Geophysics, 2022)

Fine mapping qKRN5.04 provides a functional gene negatively regulating maize kernel row number - Yixin An; Lin Chen; Yong-Xiang Li; Chunhui Li; Yunsu Shi; Dengfeng Zhang; Yu Li; Tianyu Wang (Theoretical and Applied Genetics, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Chaperone-mediated Autophagy Regulates Cell Growth by Targeting SMAD3 in Glioma - Hanqun Liu; Yuxuan Yong; Xingjian Li; Panghai Ye; Kai Tao; Guoyou Peng; Mingshu Mo; Wenyuan Guo; Xiang Chen; Yangfu Luo; Yuwan Lin; Jiewen Qiu; et al. (Neuroscience Bulletin, 2022)

Combined System of Organic Substrate and Straw-Degrading Microbial Agents Improved Soil Organic Matter Levels and Microbial Abundance in a Rice–Wheat Rotation - Shi-Li Song; Xue Luo; Hao Wu; Xiao-Lin Lu; Fang-Ji Xu; Zhen-Hua Zhang; Yong-Xiang Guan; Chuan-Chao Dai (Current Microbiology, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Secoiridoid glycosides from the fruits of Cornus officinalis - Xin Wang; Xiang-Jian Zhong; Na Zhou; Lin-Lin Ji; Jin-Jie Li; Ning Cai; Qing-Bo Wang; Peng-Cheng Lin; Xiao-Ya Shang (Natural Product Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Functional traits explain the consistent resistance of biodiversity to plant invasion under nitrogen enrichment - Shao‐peng Li; Pu Jia; Shu‐ya Fan; Yingtong Wu; Xiang Liu; Yani Meng; Yue Li; Wen‐sheng Shu; Jin‐tian Li; Lin Jiang (Ecology Letters, 2022)
Elton's biotic resistance hypothesis, which posits that diverse communities should be more resistant to biological invasions, has received considerable experimental support. However, it remains unclear whether such a negative diversity–invasibility relationship would persist under anthropogenic environmental change. By using the common ragweed ( Ambrosia artemisiifolia ) as a model invader, our 4‐year grassland experiment demonstrated consistently negative relationships between resident species diversity and community invasibility, irrespective of nitrogen addition, a result further supported by a meta‐analysis. Importantly, our experiment showed that plant diversity consistently resisted invasion simultaneously through increased resident biomass, increased trait dissimilarity among residents, and increased community‐weighted means of resource‐conservative traits that strongly resist invasion, pointing to the importance of both trait complementarity and sampling effects for invasion resistance even under resource enrichment. Our study provides unique evidence that considering species’ functional traits can help further our understanding of biotic resistance to biological invasions in a changing environment.

Hemorrhage-Induced Sphingosine Kinase 1 Contributes to Ferroptosis-Mediated Secondary Brain Injury in Intracerebral Hemorrhage - Xiaojun Diao; Qi Cui; Ning Tian; Zixian Zhou; Wenjing Xiang; Yanlin Jiang; Jungang Deng; Hongzhan Liao; Xiaohui Lin; Qinghua Li; Rujia Liao (Molecular Neurobiology, 2022)

Comprehensive review on catalytic degradation of Cl-VOCs under the practical application conditions - Fawei Lin; Li Xiang; Zhiman Zhang; Na Li; BeiBei Yan; Chi He; Zhengping Hao; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2022)

Effect of Sodium Salicylate on Calcium Currents and Exocytosis in Cochlear Inner Hair Cells: Implications for Tinnitus Generation - Ting Fan; Meng-Ya Xiang; Ruo-Qiao Zhou; Wen Li; Li-Qin Wang; Peng-Fei Guan; Geng-Lin Li; Yun-Feng Wang; Jian Li (Neuroscience Bulletin, 2022)

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Bioactive compounds derived from the marine-derived fungus MCCC3A00951 and their influenza neuraminidase inhibition activity in vitro and in silico - Shun-Zhi Liu; Feng-Ming He; Yan-lin Bin; Chu-Fang Li; Bao-Ying Xie; Xi-Xiang Tang; Ying-Kun Qiu (Natural Product Research, 2021)

An innovative echo detection system with STM32 gated and PMT adjustable gain for airborne LiDAR - Guoqing Zhou; Weihao Li; Xiang Zhou; Yizhi Tan; Gangchao Lin; Xianxing Li; Ronghua Deng (International Journal of Remote Sensing, 2021)

The Key Regulator of Necroptosis, RIP1 Kinase, Contributes to the Formation of Astrogliosis and Glial Scar in Ischemic Stroke - Yong-Ming Zhu; Liang Lin; Chao Wei; Yi Guo; Yuan Qin; Zhong-Sheng Li; Thomas A. Kent; Claire E. McCoy; Zhan-Xiang Wang; Yong Ni; Xian-Yong Zhou; Hui-Ling Zhang (Translational Stroke Research, 2021)
Necroptosis initiation relies on the receptor-interacting protein 1 kinase (RIP1K). We recently reported that genetic and pharmacological inhibition of RIP1K produces protection against ischemic stroke-induced astrocytic injury. However, the role of RIP1K in ischemic stroke-induced formation of astrogliosis and glial scar remains unknown. Here, in a transient middle cerebral artery occlusion (tMCAO) rat model and an oxygen and glucose deprivation and reoxygenation (OGD/Re)-induced astrocytic injury model, we show that RIP1K was significantly elevated in the reactive astrocytes. Knockdown of RIP1K or delayed administration of RIP1K inhibitor Nec-1 down-regulated the glial scar markers, improved ischemic stroke-induced necrotic morphology and neurologic deficits, and reduced the volume of brain atrophy. Moreover, knockdown of RIP1K attenuated astrocytic cell death and proliferation and promoted neuronal axonal generation in a neuron and astrocyte co-culture system. Both vascular endothelial growth factor D (VEGF-D) and its receptor VEGFR-3 were elevated in the reactive astrocytes; simultaneously, VEGF-D was increased in the medium of astrocytes exposed to OGD/Re. Knockdown of RIP1K down-regulated VEGF-D gene and protein levels in the reactive astrocytes. Treatment with 400 ng/ml recombinant VEGF-D induced the formation of glial scar; conversely, the inhibitor of VEGFR-3 suppressed OGD/Re-induced glial scar formation. RIP3K and MLKL may be involved in glial scar formation. Taken together, these results suggest that RIP1K participates in the formation of astrogliosis and glial scar via impairment of normal astrocyte responses and enhancing the astrocytic VEGF-D/VEGFR-3 signaling pathways. Inhibition of RIP1K promotes the brain functional recovery partially via suppressing the formation of astrogliosis and glial scar. Graphical Abstract

Linking circular intronic RNA degradation and function in transcription by RNase H1 - Xiang Li; Jia-Lin Zhang; Yun-Ni Lei; Xiao-Qi Liu; Wei Xue; Yang Zhang; Fan Nan; Xiang Gao; Jun Zhang; Jia Wei; Li Yang; Ling-Ling Chen (Science China Life Sciences, 2021)

Rapid visual genotyping method for germline mutants with small genomic fragment deletion by allele-specific PCR and lateral flow nucleic acid biosensor - Qiuju Su; Xiang Zhou; Tianwen Wu; Kui Li; Wentao Xu; Zhenyu Lin; Ping Shen; Bang Liu (Molecular Biology Reports, 2021)

Sediment Coarsening in Tidal Flats and Stable Coastline of the Abandoned Southern Yellow River Sub-Delta in Response to Fluvial Sediment Flux Decrease During the Past Decades - Lin Zeng; Chao Zhan; Qing Wang; Xianbin Liu; Longsheng Wang; Xueyan Li; Xin Wang; Xiang Yu; Jinzhi Zhang; Buli Cui (Frontiers in Marine Science, 2021)
Due to remarkable reduction of sediment supply, the vulnerability of Yellow River deltaic system increased and ecological impacts occurred to some extent. To have a comprehensive and quantitative understanding of the morphological evolution of deltas, surficial sediments of tidal flat along the abandoned southern Yellow River sub-delta and two adjacent coastal units were systematically collected and evaluated by grain-size analysis in the study. The results reveal that surficial sediments of the abandoned southern Yellow River sub-delta have been coarsening significantly since the 1980s, as characterized by a decrease in both the mud content and the clay/mud ratio. In particular, the transition from cohesive to non-cohesive sediment was completed between 2007 and 2013. With a sharp decrease in sediment flux from the Yellow River estuary, the flood currents from the submarine coastal slope carry few fine particles into the tidal zone, whereas the ebb currents with reverse direction remove some fine particles from the tidal flat. This is a major cause of sediment coarsening in the tidal flat. As sediment coarsening, the coastline of the abandoned southern Yellow River sub-delta has remained stable. The significant change in the grain size of the tidal flat surficial sediments may have a profound impact on the future coastal geomorphic evolution.

Research on a new cationic polyacrylamide (CPAM) with a cationic microblock structure and its enhanced effect on sludge condition and dewatering - Yuning Chen; Xuhao Li; Wang Zizeng; Li Feng; Jiehong Xie; Zeluan Lin; Zhihong Xu; Bingzhi Liu; Xiang Li; Huaili Zheng (Environmental Science and Pollution Research, 2021)

Characteristics of expanded polystyrene microplastics on island beaches in the Pearl River Estuary: abundance, size, surface texture and their metals-carrying capacity - Qun Xie; Heng-Xiang Li; Lang Lin; Zhen-Liang Li; Jian-sheng Huang; Xiang-Rong Xu (Ecotoxicology, 2021)

Correction to: A failure case study of tunnel water inrush source identified by statistical analysis model - Li-Gang Yuan; Xiao-Li Li; Xin Li; Yi-Lin Yu; Li-Guang Chen; Xian-Pan Xu; Xiang Wang (Arabian Journal of Geosciences, 2021)

Size Effect and Anisotropy in a Transversely Isotropic Rock Under Compressive Conditions - Kaihui Li; Zhen-Yu Yin; Dongya Han; Xiang Fan; Rihong Cao; Hang Lin (Rock Mechanics and Rock Engineering, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Metagenomic analysis revealed the sulfur- and iron- oxidation capabilities of heterotrophic denitrifying sludge - Kailong Huang; Qiaoling Li; Haohao Sun; Xu-Xiang Zhang; Hongqiang Ren; Lin Ye (Ecotoxicology, 2021)

A Multilevel Recognition Model of Water Inrush Sources: A Case Study of the Zhaogezhuang Mining Area - Gang Lin; Dong Jiang; Donglin Dong; Jingying Fu; Xiang Li (Mine Water and the Environment, 2021)

A failure case study of tunnel water inrush source identified by statistical analysis model - Li-Gang Yuan; Xiao-Li Li; Xin Li; Yi-Lin Yu; Li-Gang Chen; Xian-Pan Xu; Xiang Wang (Arabian Journal of Geosciences, 2021)

Terpenoids from the South China Sea soft coral Sinularia multiflora - Zheng Wang; Ping-Lin Li; Xiang-Chao Luo; Qi Wang; Leen van Ofwegen; Xu-Li Tang; Guo-Qiang Li (Natural Product Research, 2021)

Study on Microwave Heating Order and Electromagnetic Characteristics of Copper and Gold Ores - Feng Lin; Xia-Ting Feng; Gao-Ming Lu; Xiang-Xin Su; Shi-Ping Li; Jiu-yu Zhang (Rock Mechanics and Rock Engineering, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Control System Design and Implementation at Flexible, Distributed Offshore Sensor Test Sites in the Yangtze Estuary Area - Qingsong Hu; Chao Jiang; Lin Du; Jun Li; Leilei Chen; Peng Xiang; Hongcheng Zhang; Hafiz Abd ur Rahman (Journal of Ocean University of China, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

Alternation of soil bacterial and fungal communities by tomato–rice rotation in Hainan Island in Southeast of China - Xiang Ma; Minglun Du; Peng Liu; Yanqiong Tang; Hong Li; Qianhua Yuan; Yunze Ruan; Lei Meng; Jiachao Zhang; Min Lin; Zhu Liu (Archives of Microbiology, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Phylogenetic analysis of infectious bronchitis virus circulating in southern China in 2016–2017 and evaluation of an attenuated strain as a vaccine candidate - Libin Chen; Bin Xiang; Yanfen Hong; Qian Li; Haoyun Du; Qiuyan Lin; Ming Liao; Tao Ren; Chenggang Xu (Archives of Virology, 2021)

Flower biology and ontogeny of the tung tree (Vernicia fordii Hemsl.) - Wenying Li; Meilan Liu; Xiang Dong; Heping Cao; Ye Wu; Hai Shang; Huimeng Huang; Lin Zhang (Trees, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Erythropoietin-Induced Autophagy Protects Against Spinal Cord Injury and Improves Neurological Function via the Extracellular-Regulated Protein Kinase Signaling Pathway - Lin Zhong; Hui Zhang; Zheng-Fei Ding; Jian Li; Jin-Wei Lv; Zheng-Jun Pan; De-Xiang Xu; Zong-Sheng Yin (Molecular Neurobiology, 2020)

A study on the application of the distributed optical fiber sensing monitoring technology in the process of dismantling temporary tunnel shoring - Zi-Xiang Li; Gong-Yu Hou; Tao Hu; Tian-Ci Zhou; Hai-Lin Xiao (Arabian Journal of Geosciences, 2020)

Tyrosine Hydroxylase Gene Polymorphisms Contribute to Opioid Dependence and Addiction by Affecting Promoter Region Function - Jun-lin Liu; Shao-qing Li; Feng Zhu; Yu-xiang Zhang; Ya-nan Wu; Jing-si Yang; Bao Zhang; Chun-xia Yan (NeuroMolecular Medicine, 2020)

Immune effect of a Newcastle disease virus DNA vaccine with IL-12 as a molecular adjuvant delivered by electroporation - Peng Xie; Yanling Li; Yaling Li; Jianpeng Liang; Bin Xiang; Qiuyan Lin; Jiaqi Jin; Chan Ding; Chenggang Xu; Tao Ren (Archives of Virology, 2020)

Prenylated isoflavones with potential antiproliferative activities from Mappianthus iodoides - Yan-Ping Liu; Li-Li Sun; Xiang-Lin Zhang; Hai-Yuan Niu; Zheng-Hong Pan; Yan-Hui Fu (Natural Product Research, 2020)

Anthraquinone derivatives from a coral associated fungus Stemphylium lycopersici - Jiao Li; Yu-Bing Zheng; Tibor Kurtán; Ming-Xiang Liu; Hua Tang; Chun-Lin Zhuang; Wen Zhang (Natural Product Research, 2020)

Five new ent -kaurane diterpenes from Annona squamosa L. pericarps - Ya-Yun Chen; Cheng-Yao Ma; Mao-Lin Wang; Jia-Hui Lu; Peng Hu; Jian-Wei Chen; Xiang Li; Yong Chen (Natural Product Research, 2020)

Three new pterocarpans from the aerial parts of Abrus Precatorius - Yan Li; Jie-Wei Wu; Hai-Bo Tan; Bai-Lin Li; Sheng-Xiang Qiu (Natural Product Research, 2020)

Whole brain radiotherapy induces cognitive dysfunction in mice: key role of gut microbiota - Xiao-Xiao Luo; Chun Yang; Gao-Feng Zhan; Shan Li; Dong-Yu Hua; Ai-Lin Luo; Xiang-Lin Yuan (Psychopharmacology, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Comparative transcriptomic analysis of fireflies (Coleoptera: Lampyridae) to explore the molecular adaptations to fresh water - Qi‐Lin Zhang; Hong‐Wei Li; Zhi‐Xiang Dong; Xiao‐Jie Yang; Lian‐Bing Lin; Jun‐Yuan Chen; Ming‐Long Yuan (Molecular Ecology, 2020)
Aquatic insects are well adapted to freshwater environments, but the molecular basis of these adaptations remains largely unknown. Most firefly species (Coleoptera: Lampyridae) are terrestrial, but the larvae of several species are aquatic. Here, larval and adult transcriptomes from Aquatica leii (freshwater) and Lychnuris praetexta (terrestrial) were generated to test whether the genes associated with metabolic efficiency and morphology have undergone adaptive evolution to fresh water. The aquatic fireflies had a significantly lower ratio of nonsynonymous to synonymous substitutions than the terrestrial insects, indicating a genomewide evolutionary constraint in the aquatic fireflies. We identified 341 fast‐evolving genes and 116 positively selected genes in the aquatic fireflies. Of these, 76 genes exhibiting both fast evolution and positive selection were primarily involved in ATP production, energy metabolism and the hypoxia response. We identified 7,271 differentially expressed genes (DEGs) in A . leii (adults versus larvae) and 8,309 DEGs in L . praetexta (adults versus larvae). DEGs specific to the aquatic firefly ( n = 1,445) were screened via interspecific comparisons ( A . leii versus L . praetexta ) and were significantly enriched for genes involved in metabolic efficiency (e.g., ATP production, hypoxia, and immune responses) and certain aspects of morphology (e.g., cuticle chitin, tracheal and compound eye morphology). These results indicate that sequence and expression‐level changes in genes associated with both metabolic efficiency and morphological attributes related to the freshwater lifestyle contributed to freshwater adaptation in fireflies. This study provides new insights into the molecular mechanisms of aquatic adaptation in insects.

Modulation of copper-induced antioxidant defense, Cu transport, and mitophagy by hypoxia in the large yellow croaker (Larimichthys crocea) - Yun Pan; Chun-Xiang Ai; Lin Zeng; Can Liu; Wen-Cheng Li (Fish Physiology and Biochemistry, 2020)

The occurrence and spatial distribution of phthalate esters (PAEs) in the Lanzhou section of the Yellow River - Xia Zhao; Ji-min Shen; Hang Zhang; Xiang Li; Zhong-lin Chen; Xiao-chun Wang (Environmental Science and Pollution Research, 2020)

Spatial Relationships of Water Resources with Energy Consumption at Coal Mining Operations in China - Gang Lin; Dong Jiang; Jingying Fu; Donglin Dong; Wenjie Sun; Xiang Li (Mine Water and the Environment, 2020)

Chemical constituents from the deep sea-derived Streptomyces xiamenensis MCCC 1A01570 and their effects on RXRα transcriptional regulation - Wei-Xiang Lin; Chun-Lan Xie; Mi Zhou; Man-Li Xia; Ting-Ting Zhou; Hai-Feng Chen; Xian-Wen Yang; Quan Yang (Natural Product Research, 2020)

Hyperspectral anomaly detection by local joint subspace process and support vector machine - Pei Xiang; Huixin Zhou; Huan Li; Shangzhen Song; Wei Tan; Jiangluqi Song; Lin Gu (International Journal of Remote Sensing, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Accounting for Mine Water in Coal Mining Activities and its Spatial Characteristics in China - Gang Lin; Donglin Dong; Xiang Li; Peiwei Fan (Mine Water and the Environment, 2020)

Analysis of Cerebrospinal Fluid Soluble TREM2 and Polymorphisms in Sporadic Parkinson’s Disease in a Chinese Population - Guoyou Peng; Jiewen Qiu; Hanqun Liu; Miaomiao Zhou; Shuxuan Huang; Wenyuan Guo; Yuwan Lin; Xiang Chen; Zhe Li; Guihua Li; Wenlong Zhang; Yunlong Zhang; et al. (Journal of Molecular Neuroscience, 2020)

Morphological characteristics and genetic diversity of Colletotrichum horii infecting persimmon tree in China - Quan-en Deng; Xiang-yang Ding; Jian-an Li; Lin-kai Cui; Jian-qiang Xu (European Journal of Plant Pathology, 2020)

Circ_ANKIB1 stabilizes the regulation of miR-19b on SOCS3/STAT3 pathway to promote osteosarcoma cell growth and invasion - Yi-xin Du; Lin-xin Guo; Han-song Pan; Yi-min Liang; Xiang Li (Human Cell, 2020)

Quantitatively ranking the influencing factors of ammonia volatilization from paddy soils by grey relational entropy - Wen-Ming Xie; Shi-Jun Li; Wei-Ming Shi; Hai-Lin Zhang; Fang Fang; Guo-Xiang Wang; Li-Min Zhang (Environmental Science and Pollution Research, 2020)

Mechanistic examination of methimazole-induced hepatotoxicity in patients with Grave’s disease: a metabolomic approach - Xuesong Li; Jialin Yang; Shasha Jin; Yu Dai; Yujuan Fan; Xiaofang Fan; Zhigang Li; Jianhua Yang; Wai-Ping Yau; Haishu Lin; Weimin Cai; Xiaoqiang Xiang (Archives of Toxicology, 2020)

Characterization and fine mapping of qkrnw4, a major QTL controlling kernel row number in maize - Ningning Nie; Xiaoyu Ding; Lin Chen; Xun Wu; Yixin An; Chunhui Li; Yanchun Song; Dengfeng Zhang; Zhizhai Liu; Tianyu Wang; Yu Li; Yong-xiang Li; et al. (Theoretical and Applied Genetics, 2019)

Gedunin Degrades Aggregates of Mutant Huntingtin Protein and Intranuclear Inclusions via the Proteasomal Pathway in Neurons and Fibroblasts from Patients with Huntington’s Disease - Weiqi Yang; Jingmo Xie; Qiang Qiang; Li Li; Xiang Lin; Yiqing Ren; Wenlei Ren; Qiong Liu; Guomin Zhou; Wenshi Wei; Hexige Saiyin; Lixiang Ma (Neuroscience Bulletin, 2019)

Cloning and expression analysis of the StCUL1 gene in potato - Peng-Xiang Pang; Li Shi; Xiao-Juan Wang; Yan-Nan Chang; Yong-Ping Luo; Jin-Lin Feng; Hemu Eri; Gang Gao (Journal of Plant Biochemistry and Biotechnology, 2019)

Combining the Fisher Feature Extraction and Support Vector Machine Methods to Identify the Water Inrush Source: A Case Study of the Wuhai Mining Area - Donglin Dong; Zhiyuan Chen; Gang Lin; Xiang Li; Ruomeng Zhang; Yuan Ji (Mine Water and the Environment, 2019)

Chronology of coastal aeolian deposition and its paleoenvironmental implications on the Liuao Peninsula of South China - Jian-hui Jin; Zhi-zhong Li; Zhi-yong Ling; Fei Zheng; Xiao-lin Xu; Yan Cheng; Xiang-dong Cao; Zhi-xing Li; Wen-jing Zhang; Yong-qing Ren (Journal of Mountain Science, 2019)

A Novel Event Detection Model for Water Distribution Systems Based on Data-Driven Estimation and Support Vector Machine Classification - Xiang-Yun Zou; Yi-Li Lin; Bin Xu; Zi-Bo Guo; Sheng-Ji Xia; Tian-Yang Zhang; An-Qi Wang; Nai-Yun Gao (Water Resources Management, 2019)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

Leaf Senescence can be Induced by Inhibition of Root Respiration - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zhu-yu Gu; Fan-jiang Zeng (Journal of Plant Growth Regulation, 2019)

Characterization of the complete chloroplast genome of Euryodendron excelsum (Pentaphylacaceae), a critically endangered species endemic to China - Xiang-gang Shi; Wei-xi Li; Fen Xing; Yu-bin Zhou; Wu-xia Guo; Ye-lin Huang (Conservation Genetics Resources, 2019)

Simulating and assessing the evolution of collapsing gullies based on cellular automata-Markov and landscape pattern metrics: a case study in Southern China - Xiang Ji; Anita Thompson; Jinshi Lin; Fangshi Jiang; Shaoxin Li; Mingming Yu; Yanhe Huang (Journal of Soils and Sediments, 2019)

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Permanent displacement models of earthquake-induced landslides considering near-fault pulse-like ground motions - Ying-bin Zhang; Chen-lin Xiang; Yan-long Chen; Qian-gong Cheng; Li Xiao; Peng-cheng Yu; Zhi-wang Chang (Journal of Mountain Science, 2019)

Dynamic monitoring of resuspension in the multiple eco-types of the littoral zone of a shallow wind-disturbed lake - Chuang Qi; Yang Zhou; Xiao-guang Xu; Li-min Zhang; Hui Lin; Xin-ting Wu; Kuan Shi; Guo-xiang Wang (Aquatic Sciences, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Early Jurassic highly fractioned rhyolites and associated sedimentary rocks in southern Tibet: constraints on the early evolution of the Neo-Tethyan Ocean - Chao Wang; Lin Ding; Li-Yun Zhang; Xiang-Li Ding; Ya-Hui Yue (International Journal of Earth Sciences, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Impacts of Land Cover Changes on Ecosystem Carbon Stocks Over the Transboundary Tumen River Basin in Northeast Asia - Hengxing Xiang; Mingming Jia; Zongming Wang; Lin Li; Dehua Mao; Da Zhang; Guishan Cui; Weihong Zhu (Chinese Geographical Science, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Opioid Exposure is Associated with Aberrant DNA Methylation of OPRM1 Promoter Region in a Chinese Han Population - Jiawei Xu; Teng Wang; Zhiyang Su; Xinyao Zhou; Yuqian Xiang; Lin He; Candong Li; Zhaoyang Yang; Xinzhi Zhao (Biochemical Genetics, 2018)

Spatial-temporal characteristics of epilithic algae succession on artificial substrata in relation to water quality in Erhai Lake, Yunnan Province, China - Bo Lan; Hailan Li; Xianfen Xiang; Junjie Lin; Jing Yin; Shao Yang (Biologia, 2018)

Taraxasterol suppresses the growth of human liver cancer by upregulating Hint1 expression - Tianhao Bao; Yang Ke; Yifan Wang; Weiwei Wang; Yuehua Li; Yan Wang; Xiang Kui; Qixin Zhou; Han Zhou; Cheng Zhang; Dongming Zhou; Lin Wang; et al. (Journal of Molecular Medicine, 2018)

Intervention Effect of Repetitive TMS on Behavioral Adjustment After Error Commission in Long-Term Methamphetamine Addicts: Evidence From a Two-Choice Oddball Task - Qiongdan Liang; Jia Lin; Jiemin Yang; Xiang Li; Yijiang Chen; Xianxin Meng; Jiajin Yuan (Neuroscience Bulletin, 2018)

c.835-5T>G Variant in SMN1 Gene Causes Transcript Exclusion of Exon 7 and Spinal Muscular Atrophy - Shuang Wu; Yun-Lu Li; Ning-Yi Cheng; Chong Wang; En-Lin Dong; Ying-Qian Lu; Jin-Jing Li; Xin-Xin Guo; Xiang Lin; Lu-Lu Lai; Zhi-Wei Liu; Ning Wang; et al. (Journal of Molecular Neuroscience, 2018)

Polycyclic aromatic hydrocarbons (PAHs) in multi-phases from the drinking water source area of the Pearl River Delta (PRD) in South China: Distribution, source apportionment, and risk assessment - Yunjiang Yu; Ziling Yu; Zhengdong Wang; Bigui Lin; Liangzhong Li; Xichao Chen; Xiaohui Zhu; Mingdeng Xiang; Ruixue Ma (Environmental Science and Pollution Research, 2018)

CpG-PEG Conjugates and their Immune Modulating Effects after Systemic Administration - Caixing Wu; Xiaofei Xiang; Yang Yue; Lin Li; Yesen Li; Chong Zhang; Yuhong Xu (Pharmaceutical Research, 2018)

Characterization and fine mapping of qkc7.03: a major locus for kernel cracking in maize - Mingtao Yang; Lin Chen; Xun Wu; Xing Gao; Chunhui Li; Yanchun Song; Dengfeng Zhang; Yunsu Shi; Yu Li; Yong-xiang Li; Tianyu Wang (Theoretical and Applied Genetics, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

A new ent -kaurane diterpene derivative from the stems of Eurya chinensis R.Br - Jia-Ling Song; Yao Yuan; Ling-Hui Nie; Bai-Lin Li; Xu-Bing Qin; Yan Li; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2018)

Variations of Laohugou Glacier No. 12 in the western Qilian Mountains, China, from 1957 to 2015 - Yu-shuo Liu; Xiang Qin; Ji-zu Chen; Zhen-lin Li; Jing Wang; Wen-tao Du; Wan-qin Guo (Journal of Mountain Science, 2018)

Analysing changes of the Poyang Lake water area using Sentinel-1 synthetic aperture radar imagery - Lingfang Zeng; Michael Schmitt; Lin Li; Xiao Xiang Zhu (International Journal of Remote Sensing, 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

Yangonindimers A-C, three new kavalactone dimers from Piper methysticum (kava) - Jia-Ling Song; Bai-Lin Li; Yao Yuan; Ling-Hui Nie; Jia Niu; David Chiu; Zhi-Fang Xu; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2017)

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Qiuan Zhu; Changhui Peng; Philippe Ciais; Hong Jiang; Jinxun Liu; Philippe Bousquet; Shiqin Li; Jie Chang; Xiuqin Fang; Xiaolu Zhou; Huai Chen; Shirong Liu; et al. (Global Change Biology, 2017)
Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Stable isotope tracing of headwater sources in a river on China’s Loess Plateau - Zhi Li; Xueqing Lin; Wei Xiang; Xi Chen; Tianming Huang (Hydrological Sciences Journal, 2017)

Design, synthesis, antitumor evaluation, 3D-QSAR and molecular docking studies of novel 4-aminoacridone compounds - Lin Tian; Chang J. Feng; Tong X. Li; Zhao Li; Wei H. Yang; Xiang E. Han (Medicinal Chemistry Research, 2017)

Secretory expression of a novel human spermatozoa antigen in E. coli and its application to a protein chip - Ming-zhu Wang; Zhuo-lin Qiu; Xiang-Sheng Cai; Jing-jing Li; Miao-qin She; Yuan-feng Xu; Ying-song Wu (Biotechnology Letters, 2017)

Magnesium Ions Promote the Biological Behaviour of Rat Calvarial Osteoblasts by Activating the PI3K/Akt Signalling Pathway - Jian Wang; Xiang-Yu Ma; Ya-Fei Feng; Zhen-Sheng Ma; Tian-Cheng Ma; Yang Zhang; Xiang Li; Lin Wang; Wei Lei (Biological Trace Element Research, 2017)

Quantifying soil macropore networks in different forest communities using industrial computed tomography in a mountainous area of North China - Chen Meng; Jianzhi Niu; Xiang Li; Ziteng Luo; Xiaoqing Du; Jie Du; Xingna Lin; Xinxiao Yu (Journal of Soils and Sediments, 2017)

Modern greenhouse culture of juvenile soft-shelled turtle, Pelodiscus sinensis - Jing Zhang; Fen Wang; Ye-Lin Jiang; Guan-Jun Hou; Yun-Sheng Cheng; Hong-Lian Chen; Xiang Li (Aquaculture International, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Furofuran lignan glucosides from the leaves of Vitex negundo var. cannabifolia - Yue-Ting Li; Man-Man Li; Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Dao-Ran Pang; Jiao Zheng; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

Elevated Serum and Cerebrospinal Fluid Free Fatty Acid Levels Are Associated with Unfavorable Functional Outcome in Subjects with Acute Ischemic Stroke - Xiao-Xia Duan; Guan-Peng Zhang; Xiao-Bin Wang; Hua Yu; Jia-Li Wu; Ke-Zhi Liu; Lin Wang; Xiang Long (Molecular Neurobiology, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

Anti-neuroinflammatory constituents from the fungus Penicillium purpurogenum MHZ 111 - Jing Sun; Zhi-Xiang Zhu; Yue-Lin Song; Yi Ren; Dan Dong; Jiao Zheng; Ting Liu; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Both major and minor QTL associated with plant height can be identified using near-isogenic lines in maize - Xiaoyu Ding; Xun Wu; Lin Chen; Chunhui Li; Yunsu Shi; Yanchun Song; Dengfeng Zhang; Tianyu Wang; Yu Li; Zhizhai Liu; Yong-xiang Li (Euphytica, 2017)

The Chlorophyll a Fluorescence Characteristic in Different Types of Leaf Senescence in Alhagi sparsifolia - Gang-Liang Tang; Xiang-Yi Li; Li-Sha Lin; Zhu-Yu Gu; Fan-Jiang Zeng (Journal of Plant Growth Regulation, 2016)

Surgical treatment of hepato-pancreato-biliary disease in China: the Tongji experience - Binhao Zhang; Wei Dong; Hongping Luo; Xuanru Zhu; Lin Chen; Changhai Li; Peng Zhu; Wei Zhang; Shuai Xiang; Wanguang Zhang; Zhiyong Huang; Xiao-Ping Chen (Science China Life Sciences, 2016)

Fine mapping of qKW7, a major QTL for kernel weight and kernel width in maize, confirmed by the combined analytic approaches of linkage and association analysis - Xin Li; Yong-xiang Li; Lin Chen; Xun Wu; Weiwei Qin; Yanchun Song; Dengfeng Zhang; Tianyu Wang; Yu Li; Yunsu Shi (Euphytica, 2016)

The Effect on Sodium/Iodide Symporter and Pendrin in Thyroid Colloid Retention Developed by Excess Iodide Intake - Xiao-yi Chen; Chu-hui Lin; Li-hua Yang; Wang-gen Li; Jin-wei Zhang; Wen-wei Zheng; Xiang Wang; Jiang Qian; Jia-luan Huang; Yi-xiong Lei (Biological Trace Element Research, 2016)

Improvement and comparison of the rainfall–runoff methods in SWAT at the monsoonal watershed of Baocun, Eastern China - Qin-Bo Cheng; Christian Reinhardt-Imjela; Xi Chen; Achim Schulte; Xiang Ji; Fu-Lin Li (Hydrological Sciences Journal, 2016)

Different causes of photosynthetic decline and water status in different stages of girdling in Alhagi sparsifolia Shap. (Fabaceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Fan-jiang Zeng (Brazilian Journal of Botany, 2016)

Microsatellite analysis of the genetic relationships between wild and cultivated giant grouper in the South China Sea - QING WANG; XIANG WANG; ZHENZHEN XIE; YIQI LI; LING XIAO; CHENG PENG; HAIFA ZHANG; SHUISHENG LI; YONG ZHANG; HAORAN LIN (Journal of Genetics, 2016)

Changes in the activities of starch metabolism enzymes in rice grains in response to elevated CO2 concentration - Li-Yong Xie; Er-Da Lin; Hong-Liang Zhao; Yong-Xiang Feng (International Journal of Biometeorology, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Correlation between the germline methylation status in ERβ promoter and the risk in prostate cancer: a prospective study - Lihui Wang; Pan Zhang; Xiannan Meng; Xiang Chen; Zou Xiang; Xiaoqian Lin; Ye Liu; Weidong Gan; Xiaodong Han; Dongmei Li (Familial Cancer, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

Particle-Associated Ambient Benzo[a]pyrene and Levels of Urinary 1-Hydroxypyrene in a Non-occupationally Exposed Population of Adults and Children in Lanzhou, China - Yunjiang Yu; Qiong Wang; Liangzhong Li; Zien Liu; Peng Sun; Yanping Zhang; Haipeng Lin; Mingdeng Xiang; Hui Li; Bigui Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Cytotoxicity and mutagenicity of sidestream cigarette smoke particulate matter of different particle sizes - Xiang Li; Bencheng Lin; Huashan Zhang; Fuwei Xie; Na Ta; Lei Tian; Huimin Liu; Zhuge Xi (Environmental Science and Pollution Research, 2016)

Clinical validation of a novel real-time human papillomavirus assay for simultaneous detection of 14 high-risk HPV type and genotyping HPV type 16 and 18 in China - Hui Yang; Lie-Jun Li; Long-Xu Xie; Zhao-Yun Luo; Min Lu; Min Lin; Xiang-bin Zheng; Yue Huang; Li-Ye Yang (Archives of Virology, 2016)

Impact of phloem girdling on water status in desert plants Alhagi sparsifolia Shap. (Fabaceae) and Karelinia Caspica (Pall.) Less. (Asteraceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zi-chun Guo; Chang-jun Li; Hui Guo; Fan-jiang Zeng (Brazilian Journal of Botany, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

OsKASI, a β-ketoacyl-[acyl carrier protein] synthase I, is involved in root development in rice (Oryza sativa L.) - Wona Ding; Li Lin; Botao Zhang; Xianbo Xiang; Jing Wu; Zhichong Pan; Shihua Zhu (Planta, 2015)

Endoplasmic Reticulum Stress: Relevance and Therapeutics in Central Nervous System Diseases - Hong-Yu Zhang; Zhou-guang Wang; Xiang-Hong Lu; Xiao-Xia Kong; Fen-Zan Wu; Li Lin; Xiaohua Tan; Li-Bing Ye; Jian Xiao (Molecular Neurobiology, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Overexpression of a maize WRKY58 gene enhances drought and salt tolerance in transgenic rice - Ronghao Cai; Yang Zhao; Yufu Wang; Yongxiang Lin; Xiaojian Peng; Qian Li; Yuwei Chang; Haiyang Jiang; Yan Xiang; Beijiu Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Proteomic changes of Citrus roots in response to long-term manganese toxicity - Xiang You; Lin-Tong Yang; Yi-Bin Lu; Huan Li; Shi-Qi Zhang; Li-Song Chen (Trees, 2014)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Photosystem II activity of typical desert plant Alhagi sparsifolia Sharp.: response to exposure to natural light after being kept in shade - Lei Li; Xiang-yi Li; Xin-wen Xu; Li-sha Lin; Fan-jiang Zeng; Feng-li Chen (Trees, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Genes in the serotonin pathway are associated with bipolar affective disorder in a Han Chinese population - Bo Xiang; Zhenxing Yang; Yin Lin; Lijie Guan; Xuan Li; Wei Deng; Zeyu Jiang; Guohui Lao; Qiang Wang; Xiaoyu Hao; Xiang Liu; Yingcheng Wang; et al. (Neuroscience Bulletin, 2014)

Effects of intercropping with Atractylodes lancea and application of bio-organic fertiliser on soil invertebrates, disease control and peanut productivity in continuous peanut cropping field in subtropical China - Xiao-gang Li; Xing-xiang Wang; Chuan-chao Dai; Tao-lin Zhang; Xing-guang Xie; Chang-feng Ding; Hong-wei Wang (Agroforestry Systems, 2014)

Effects of high temperature on the chlorophyll a fluorescence of Alhagi sparsifolia at the southern Taklamakan Desert - Lei Li; Xiang-Yi Li; Xin-Wen Xu; Li-Sha Lin; Fan-Jiang Zeng (Acta Physiologiae Plantarum, 2014)

A new indole alkaloidal glucoside from the aerial parts of Clematis terniflora DC. - Wen-Ting Li; Bing-Xian Yang; Wei Zhu; Ming-Hua Gong; Xiang-Dong Xu; Xiang-Hong Lu; Lian-Li Sun; Jing-Kui Tian; Lin Zhang (Natural Product Research, 2013)

Factors influencing the grazing management styles of settled herders: a case study of Nagqu County, Tibetan Plateau, China - Xiao-bo Hua; Jian-zhong Yan; Xiang Liu; Ying-ying Wu; Lin-shan Liu; Yi-li Zhang (Journal of Mountain Science, 2013)

Identification of MHC class I sequences in four species of Macaca of China - Xiang Yan; Aixue Li; Lin Zeng; Yuhua Cao; Jianbin He; Longbao Lv; Lihua Sui; Huahu Ye; Junwen Fan; Xiaoxia Cui; Zhaozeng Sun (Immunogenetics, 2013)

Menstrual blood-derived mesenchymal stem cells differentiate into functional hepatocyte-like cells - Xiao-zhou Mou; Jian Lin; Jin-yang Chen; Yi-fei Li; Xiao-xing Wu; Bing-yu Xiang; Cai-yun Li; Ju-ming Ma; Charlie Xiang (Journal of Zhejiang University-SCIENCE B, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

SAR image coregistration using fringe definition detection - Ying-hui Yang; Qiang Chen; Guo-xiang Liu; Zhi-lin Li; Hai-qin Cheng; Li-yao Liu (Journal of Mountain Science, 2013)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

Chlamydia inhibit host cell apoptosis by inducing Bag-1 via the MAPK/ERK survival pathway - Du Kun; Cheng Xiang-lin; Zhou Ming; Li Qi (Apoptosis, 2013)

Different Gene Expressions of Resistant and Susceptible Maize Inbreds in Response to Fusarium verticillioides Infection - Guangsheng Yuan; Zhiming Zhang; Kui Xiang; Yaou Shen; Juan Du; Haijian Lin; Li Liu; Maojun Zhao; Guangtang Pan (Plant Molecular Biology Reporter, 2013)

The member of high temperature requirement family HtrA2 participates in neuronal apoptosis after intracerebral hemorrhage in adult rats - Huiqing Sun; Lei Li; Feng Zhou; Lin Zhu; Kaifu Ke; Xiang Tan; Wei Xu; Ying Rui; Heyi Zheng; Zhengming Zhou; Huiguang Yang (Journal of Molecular Histology, 2013)

Screening Chinese soybean genotypes for Agrobacterium-mediated genetic transformation suitability - Zhang-yue Song; Jing-luan Tian; Wei-zhe Fu; Lin Li; Ling-hong Lu; Lian Zhou; Zhi-hui Shan; Gui-xiang Tang; Hui-xia Shou (Journal of Zhejiang University-SCIENCE B, 2013)

Anatomical adaptations of the xerophilous medicinal plant, Capparis spinosa, to drought conditions - Lu Gan; Chunyu Zhang; Yongtai Yin; Zhiwei Lin; Yongwei Huang; Jun Xiang; Chunhua Fu; Maoteng Li (Horticulture, Environment, and Biotechnology, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Standard spectrum measurement and simulation of elemental capture spectroscopy log - Hong-Liang Wu; Ning Li; Chang-Lin Lan; Xiang-Zhong Kong; Hua Chai (Applied Geophysics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat - Hong-Chang Gao; Huan Zhu; Cai-Yong Song; Li Lin; Yun Xiang; Zhi-Han Yan; Guang-Hui Bai; Fa-Qing Ye; Xiao-Kun Li (Molecular Neurobiology, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Combinational transformation of three wheat genes encoding fructan biosynthesis enzymes confers increased fructan content and tolerance to abiotic stresses in tobacco - Xiaomin Bie; Ke Wang; Maoyun She; Lipu Du; Shuangxi Zhang; Jiarui Li; Xiang Gao; Zhishan Lin; Xingguo Ye (Plant Cell Reports, 2012)

Pharmacophore modeling, virtual screening, and molecular docking studies for discovery of novel Carbonic anhydrase IX inhibitors - Chun-Lin Lu; Lu Zhou; Zi-Cheng Li; Xiang Gao; Wei Zhang (Medicinal Chemistry Research, 2012)

Formation of Volatile Halogenated By-Products During the Chlorination of Oxytetracycline - Bin Xu; He-Zhen Zhu; Yi-Li Lin; Kai-Yuan Shen; Wen-Hai Chu; Chen-Yan Hu; Kang-Ning Tian; Seleli Andrew Mwakagenda; Xiang-Yu Bi (Water, Air, & Soil Pollution, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Cloning and the expression pattern of Spätzle gene during embryonic development and bacterial challenge in Artemia sinica - Lu-ping Zheng; Lin Hou; Miao Yu; Xiang Li; Xiang-yang Zou (Molecular Biology Reports, 2012)

Pt and Pd in sediments from the Pearl River Estuary, South China: background levels, distribution, and source - Li-feng Zhong; Wen Yan; Jie Li; Xiang-lin Tu; Bao-ming Liu; Zhen Xia (Environmental Science and Pollution Research, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Induction of Mitogynogenetic Diploids and Identification of WW Super-female Using Sex-Specific SSR Markers in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Xiang-Shan Ji; Chang-Wei Shao; Wen-Long Li; Jing-Feng Yang; Zuo Liang; Xiao-Lin Liao; Gen-Bo Xu; Ying Xu; Wen-Tao Song (Marine Biotechnology, 2012)

Cloning and characterization of β-catenin gene in early embryonic developmental stage of Artemia sinica - Xiang Li; Lin Hou; Jian Ma; Yudong Liu; Luping Zheng; Xiangyang Zou (Molecular Biology Reports, 2012)

Effect of Different Iodine Nutrition on Cerebellum Pcp-2 in Rat Offspring During Lactation - Lu Zhang; Yi Na Sun; Yong Mei Li; Lai Xiang Lin; Yan Ye; Yu Qin Yan; Zu Pei Chen (Biological Trace Element Research, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Estimation of cancer cases and deaths attributable to infection in China - Wang Xiang; Ju-Fang Shi; Ping Li; Jian-Bing Wang; Li-Na Xu; Wen-Qiang Wei; Fang-Hui Zhao; You-Lin Qiao; Paolo Boffetta (Cancer Causes & Control, 2011)

Mapping of quantitative trait loci for fiber and lignin contents from an interspecific cross Oryza sativa × Oryza rufipogon - Jian-kun Xie; Xiang-li Kong; Jie Chen; Biao-lin Hu; Piao Wen; Jie-yun Zhuang; Jin-song Bao (Journal of Zhejiang University-SCIENCE B, 2011)

Identification and characterization of Sox genes in the silkworm, Bombyx mori - Ling Wei; Daojun Cheng; Dong Li; Meng Meng; Lina Peng; Lin Tang; Minhui Pan; Zhonghuai Xiang; Qingyou Xia; Cheng Lu (Molecular Biology Reports, 2011)

Establishment of a cerebral schistosomiasis experimental model in rabbits - Peng Wang; Dan Wang; Shi-Jie Chen; Ming-Can Wu; Xiang-Lin Cheng; Jun-Chuan Li; Ting-Xuan Chen; Zhan-Sheng Zhu (Neuroscience Bulletin, 2011)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

Characterization of Outer Membrane Proteins of Escherichia Coli in Response to Phenol Stress - Dan-Feng Zhang; Hui Li; Xiang-Min Lin; San-Ying Wang; Xuan-Xian Peng (Current Microbiology, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Geochemical and zircon U–Pb study of the Huangmeijian A-type granite: implications for geological evolution of the Lower Yangtze River belt - He Li; Hong Zhang; Ming-Xing Ling; Fang-Yue Wang; Xing Ding; Ji-Bin Zhou; Xiao-Yong Yang; Xiang-Lin Tu; Weidong Sun (International Geology Review, 2011)

Microarray-based identification of tomato microRNAs and time course analysis of their response to Cucumber mosaic virus infection - Qiu-lei Lang; Xiao-chuan Zhou; Xiao-lin Zhang; Rafal Drabek; Zhi-xiang Zuo; Yong-liang Ren; Tong-bin Li; Ji-shuang Chen; Xiao-lian Gao (Journal of Zhejiang University-SCIENCE B, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

Globular adiponectin regulates energy homeostasis through AMP-activated protein kinase–acetyl-CoA carboxylase (AMPK/ACC) pathway in the hypothalamus - Jun-Ping Wen; Chun-e Liu; Ya-Ting Hu; Gang Chen; Li-xiang Lin (Molecular and Cellular Biochemistry, 2010)

Effect of VP28 DNA vaccine on white spot syndrome virus in Litopenaeus vannamei - Xiang Li; Qing-hui Liu; Lin Hou; Jie Huang (Aquaculture International, 2010)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

Identification of p27/KIP1 expression level as a candidate biomarker of response to rapalogs therapy in human cancer - Guang Chen; Na Yang; Xiang Wang; Si-Yuan Zheng; Yi Chen; Lin-Jiang Tong; Yi-Xue Li; Ling-Hua Meng; Jian Ding (Journal of Molecular Medicine, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Assessment of the role of brine shrimp Artemia in white spot syndrome virus (WSSV) transmission - Jia-Song Zhang; Shuang-Lin Dong; Yun-Wei Dong; Xiang-Li Tian; Yi-Cheng Cao; Zuo-Jia Li; Dong-Chun Yan (Veterinary Research Communications, 2010)

Isolation and characterization of polymorphic microsatellite loci from black snapper Sebastodes fuscescens (Houttuyn) - Jing-Feng Yang; Li-Li Zhao; Chang-Wei Shao; Xiang-Shan Ji; Xiao-Lin Liao; Song-Lin Chen (Conservation Genetics, 2009)

Provenance and thermal history of the Bayan Har Group in the western‐central Songpan–Ganzi–Bayan Har terrane: Implications for tectonic evolution of the northern Tibetan Plateau - Guo‐Can Wang; Robert P. Wintsch; John I. Garver; Mary Roden‐Tice; She‐Fa Chen; Ke‐Xin Zhang; Qi‐Xiang Lin; Yun‐Hai Zhu; Shu‐Yuan Xiang; De‐Wei Li (Island Arc, 2009)
Triassic turbidites dominate the Songpan–Ganzi–Bayan Har (SGBH) terrane of the northern Tibetan Plateau. U‐Pb dating on single detrital zircon grains from the Triassic Bayan Har Group turbidites yield peaks at 400–500 m.y., 900–1000 m.y., 1800–1900 m.y., and 2400–2500 m.y., These results are consistent with recently published U‐Pb zircon ages of pre‐Triassic bedrock in the East Kunlun, Altyn, Qaidam, Qilian and Alaxa areas to the north, suggesting that provenance of the Bayan Har Group may include these rocks. The similarities in the compositions of the lithic arkosic sandstones of the Bayan Har Group with the sandstones of the Lower‐Middle Triassic formations in the East Kunlun terrane to the north also suggests a common northern provenance for both. A well exposed angular unconformity between the Carboniferous–Middle Permian mélange sequences and the overlying Upper Permian or Triassic strata indicates that regional deformation occurred between the Middle and Late Permian. This deformation may have been the result of a soft collision between the Qiangtang terrane and the North China Plate and the closure of the Paleo‐Tethyan oceanic basin. The Bayan Har Group turbidites were then deposited in a re‐opened marine basin on a shelf environment. Fission‐track dating of detrital zircons from the Bayan Har Group sandstones revealed pre‐ and post‐depositional age components, suggesting that the temperatures did not reach the temperatures necessary to anneal retentive zircon fission tracks (250–300°C). A 282–292 m.y. peak age defined by low U concentration, retentive zircons likely reflects a northern granitic source. Euhedral zircons from two lithic arkoses with abundant volcanic fragments in the southern area yielded a ∼237 m.y. zircon fission track (ZFT) peak age, likely recording the maximum age of deposition. A dominant post‐depositional 170–185 m.y. ZFT peak age suggests peak temperatures were reached in the Early Jurassic. Some samples appear to record a younger thermal event at ∼140 m.y., a short lived event that apparently affected only the least retentive zircons.

Takayasu’s arteritis associated with Crohn’s disease - You-shi Liu; You-hong Fang; Ling-xiang Ruan; You-ming Li; Lin Li; Ling-ling Jiang (Journal of Zhejiang University-SCIENCE B, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Distribution and Accumulation of Copper and Cadmium in Soil–Rice System as Affected by Soil Amendments - Ping Li; Xing-xiang Wang; Tao-lin Zhang; Dong-mei Zhou; Yuan-qiu He (Water, Air, & Soil Pollution, 2009)

Effects of early postnatal sibling deprivation on anxiety and vulnerability to cocaine in offspring rats - Yan-Qin Li; Xiao-Yi Wang; Hai-feng Zhai; Yong-Qiu Zheng; Xiang Yang Zhang; Therese Kosten; Lin Lu (Psychopharmacology, 2008)

Enhanced migration and CXCR4 over-expression in fibroblasts with telomerase reconstitution - Yi Qu; Meng Mao; Xihong Li; Lin Zhang; Xiang Huang; Chunlei Yang; Fengyang Zhao; Ying Xiong; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Mechanisms and assessment of water eutrophication - Xiao-e Yang; Xiang Wu; Hu-lin Hao; Zhen-li He (Journal of Zhejiang University-SCIENCE B, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)

Cloning and functional characterization of PpDBF1 gene encoding a DRE-binding transcription factor from Physcomitrella patens - Ning Liu; Nai-Qin Zhong; Gui-Ling Wang; Li-Juan Li; Xiang-Lin Liu; Yi-Kun He; Gui-Xian Xia (Planta, 2007)

Effect of proximal femoral osteoporosis on cementless hip arthroplasty: A short-term clinical analysis - Xian-feng Lou; Yu-hong Li; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2007)

Synergistic promotion of gibberellin and cytokinin on direct regeneration of floral buds from in vitro cultures of sepal segments in sinningia speciosa hiern - Ji-Liang Pang; Li-Lin Wang; Jiang-Qin Hu; Tai-He Xiang; Hai-Man Liang (In Vitro Cellular & Developmental Biology - Plant, 2006)

Status of Biological Studies and Aquaculture Development of the Mud Crab, Scylla serrata, in China: An Experimental Ecological Studies - Wang Gui-zhong; Li Shao-jing; Zeng Chao-shu; Lin Shu-jun; Kong Xiang-hui; Ai Chun-xiang; Lin Qiong-wu (Aquaculture International, 2005)

An efficient protocol for plant regeneration from protoplasts of the moss Atrichum undulatum P. Beauv in vitro - Lin-Hui Li; Xian-Ping Wang; Wan-Ru Hou; Xiang-Lin Liu; Yi-Kun He (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

A common IL-13 Arg130Gln single nucleotide polymorphism among Chinese atopy patients with allergic rhinitis - Min Wang; Zhi-Min Xing; Chao Lu; You-Xiang Ma; De-Lin Yu; Zheng Yan; Shen-Wu Wang; Li-Sheng Yu (Human Genetics, 2003)

Conversion of an obligate autotrophic bacteria to heterotrophic growth: expression of a heterogeneous phosphofructokinase gene in the chemolithotroph Acidithiobacillus thiooxidans - Ke Li Tian; Jian Qun Lin; Xiang Mei Liu; Ying Liu; Chang Kai Zhang; Wang Ming Yan (Biotechnology Letters, 2003)

Suppression subtractive hybridization cloning of cDNAs of differentially expressed genes in dovetree (Davidia involucrata) bracts - Yun-Xiang Li; Li Chen; Lin Juan; Yufeng Li; Fang Chen (Plant Molecular Biology Reporter, 2002)